Phosphate and nitrate isotope responses to lateral plume mixing and nutrient turnover downstream of a wastewater discharge - Daren C. Gooddy; Michael J. Bowes; Alexandra V.E. O'Brien; David J.E. Nicholls; Andi C. Smith; James P.R. Sorensen; Patrick Harrison; Stefan Krause (Applied Geochemistry, 2026)

Corrigendum to ‘Genetic linkage map of the Australian barramundi (Lates calcarifer) reveals potential to leverage extreme sex-specific recombination and sequential hermaphrodism for ultimate breeding program control’ [Aquaculture Volume 622 15 July 2026 744046] - Jessica Hintzsche; Lorenzo Vincenzo Bertola; David B. Jones; Christie Warburton; Owen Powell; Elizabeth M. Ross; Paul Harrison; Holly Cate; Dean R. Jerry; Ben J. Hayes; Kyall R. Zenger (Aquaculture, 2026)

Genetic linkage map of the Australian barramundi (Lates calcarifer) reveals potential to leverage extreme sex-specific recombination and sequential hermaphrodism for ultimate breeding program control - Jessica Hintzsche; Lorenzo V. Bertola; David B. Jones; Christie Warburton; Owen Powell; Elizabeth M. Ross; Paul Harrison; Holly S. Cate; Dean R. Jerry; Ben J. Hayes; Kyall R. Zenger (Aquaculture, 2026)

The dynamical survival of binary near-Earth asteroids: Application to (65803) Didymos, (66391) 1999 KW4, and (101955) Bennu - Rachel H. Cueva; William F. Bottke; Jay W. McMahon; David Nesvorný; Kevin J. Walsh; David Vokrouhlický; Harrison F. Agrusa (Icarus, 2026)

Comparing phosphatised galleried stereom of Ordovician Cincinnaticrinus to modern Endoxocrinus illustrates preservation by micromolding - Benjamin F. Dattilo; Rebecca L. Freeman; David F. Wright; David L. Meyer; James R. Thomka; Samuel Sheray; Michael Harrison; Christopher D. Aucoin (Facies, 2026)
Fossil echinoderm ossicles are often occluded by syntaxial overgrowths which obscure stereom. Phosphatized ossicles from insoluble residues show fine microstructure. We investigated phosphatized stereom in Cincinnaticrinus columnals in insoluble residues from the Ordovician around Cincinnati, Ohio USA. Microstructures appeared to be stereom micromolds. We tested this hypothesis by examining residue and thin sections of undissolved sample using light microscopy, SEM and EDS, resulting in these observations: (1) calcite within phosphatized ossicles is optically aligned and parallel to stem; (2) phosphate deposited centripetally from calcite surfaces, often incompletely filling cavities, leaving a central vug; (3) while calcite is inclusion-free, phosphate contains siliciclastic inclusions from surrounding sediments. These observations suggest that calcite is original, and phosphate was deposited as micromolds. To confirm the phosphatic micromold hypothesis, we compared internodal columnals from the extant isocrinid Endoxocrinus from the Florida Straits using fracture surfaces and epoxy-impregnated thin sections. We then dissolved the thin section calcite, leaving epoxy micromolds for comparison. Schematic 3-D models summarize our reconstructions of structure of the crinoids in both original calcite and micromolds. Through-going solid cylinders are present in Cincinnaticrinus phosphate and Endoxocrinus epoxy molds. In Endoxocrinus , these are molds of stereomic galleries complete with ligaments, confirming Cincinnaticrinus phosphate is also moldic. Galleried stereom of the two crinoids differs in structural details, a divergence that is consistent with phylogenetic evidence of through-going ligaments in an early common ancestor. Preservation by phosphatic micro-molding, interpreted as preserved negative space, facilitates study of stereomic features supporting crinoid soft tissues.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Assessing Potential Data Sources for Landscape-scale Terrestrial Biodiversity Indicators - Tom Bradfer-Lawrence; Meriel Harrison; Adham Ashton-Butt; Sophie Bennett; Robin J. Boyd; Ella Browning; Graeme Buchanan; Adam Fraser; Sian E. Green; Robert Hawkes; Becky E. Heath; Pen-Yuan Hsing; et al. (Environmental Management, 2026)

On the interpretation of biogenic carbon flows in livestock LCAs: A comment on - Andre M. Mazzetto; Aaron T. Simmons; Beverley Henry; Christophe d'Abbadie; David Styles; Göran Berndes; Maartje Sevenster; Matthew T. Harrison; Richard Eckard; Warwick B. Badgery; Annette Cowie (Agricultural Systems, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Astaxanthin, meclizine, mitoglitazone, pioglitazone, alpha-ketoglutarate, mifepristone, methotrexate, and atorvastatin-telmisartan do not increase lifespan in UM-HET3 mice - Ron Korstanje; Randy Strong; Adam B. Salmon; Molly A. Bogue; Sean P. Curran; Vivian Diaz; Elizabeth Fernandez; Brett Ginsburg; Melissa Han; David E. Harrison; Catherine Kaczorowski; Matt Kaeberlein; et al. (GeroScience, 2026)

Determinants of L-band backscatter in dry tropical ecosystems: Implications for biomass mapping - João M.B. Carreiras; Thomas Higginbottom; John L. Godlee; Sam Harrison; Lorena Benitez; Penelope J. Mograbi; Aurora Levesley; Karina Melgaço; David Milodowski; Georgia Pickavance; Geoff Wells; Edmar Almeida de Oliveira; et al. (Remote Sensing of Environment, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Leading Indicators for Farmers’ Work Health and Safety in Western Agricultural Systems: A Systematic Review - Carlos Mesa Castrillon; Kerri-Lynn Peachey; Lisa Harrison; Richard Franklin; David Lyle; Tony Lower (Journal of Agromedicine, 2026)

Mitochondrial dysfunction drives age-related degeneration of the thoracic aorta - Arjune S. Dhanekula; Benjamin R. Harrison; Gavin Pharaoh; Aurora Mattson-Hughes; Stefano Tarantini; Rudolph Stuppard; Scott C. DeRoo; Christopher R. Burke; Billiana Hwang; Jay D. Pal; Michael S. Mulligan; David J. Marcinek (GeroScience, 2025)

The natural products magnetic resonance database (NP-MRD): comprehensive resource for natural products NMR data enabling discovery and understanding - John R. Cort; Jessica L. Bade; Roger G. Linington; Matthew Pin; Ella F. Poynton; Lloyd W. Sumner; James T. Koller; Zachary M. Tretter; Bharat Goel; David S. Wishart; Vasuk Gautam; Scott McKay; et al. (Phytochemistry Letters, 2025)

Diversification of kratom alkaloids using biocatalysis for opioid use disorders - Sahar Amin; Hannah Boesger; Natalia R. Harris; Kayla Kroning; Harrison Snodgrass; Wenjing Wang; Jared Lewis; David H. Sherman (Phytochemistry Letters, 2025)

Extension of lifespan by epicatechin, halofuginone and mitoglitazone in male but not female genetically heterogeneous mice - Randy Strong; James F. Nelson; Molly A. Bogue; Jerry R. Colca; Martin Denzel; Vivian Diaz; Brian N. Finck; Vadim N. Gladyshev; Steve Horvath; Nisi Jiang; Tracy Keller; Rolf F. Kletzien; et al. (GeroScience, 2025)
Mice bred in 2021 were tested by the Interventions Testing Program (ITP) for possible lifespan benefits of 2BAct (2BA), dichloroacetate (DCA), Epicatechin (EPI), Forskolin (FSK), Halofuginone (HAL) and Mitoglitazone (MIT). All agents were administered in the diet ad libitum beginning at 7 months of age. In male mice, EPI increased median lifespan by ~ 5%, and HAL and MIT each increased median lifespan by ~ 9%. EPI and HAL, but not MIT, increased 90% survival. In addition to adding 3 new agents to the list of interventions identified by the ITP that extend lifespan, this report continues the strong male bias in the efficacy of life-extending drugs identified so far.

End-of-life pathology in UM-HET3 mice treated with 16 α‑hydroxyestradiol or late‑start canagliflozin - Jessica M. Snyder; David E. Harrison; Ron Korstanje; Brett Ginsburg; Peter C. Reifsnyder; James Nelson; Scott Leiser; Catherine Kaczorowski; Denise M. Imai; Adam B. Salmon; Randy Strong; Warren Ladiges; et al. (GeroScience, 2025)
Canagliflozin (Cana) started at 16 months of age and 16-hydroxy-estradiol (OH_Est) started at 12 months each led to significant increases in lifespan in male UM-HET3 mice but significant decreases in female lifespan. To seek insights into the basis for these sex-specific effects, we performed end-of-life histopathological analyses of control and treated mice for all three interventions testing program sites. There were no significant drug-induced alterations in inferred cause of death, although statistical power was low for such comparisons. Tabulation of incidental lesions (i.e., combining lethal and non-lethal lesions) revealed a complex set of significant and near-significant changes caused by each of the two agents, in some cases absent, or even opposite in direction, in one of the two sexes. The analysis did not, however, reveal a clear pattern that would explain the selective sex-specific effects of either agent on lifespan. It is plausible that the female-specific harm induced by each of these agents could reflect harmful or toxic effects that are not easily detectable by histopathological examination.

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16-hydroxyestradiol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Accuracies of genomic prediction accounting for genotype by environment remain high when using small sets of selected SNPs in barramundi Lates calcarifer - Cecile Massault; David B. Jones; Marie Lillehammer; Holly Cate; Paul Harrison; Jan M. Strugnell; Kyall R. Zenger; Nicholas A. Robinson; Dean R. Jerry (Aquaculture, 2025)

Potential bedrock exposures of Schrödinger impact melt sheet and/or polymict impact breccias within a crater floor fracture system and volcanic vent - David A. Kring; Valentin T. Bickel; Pascal Lee; Amy L. Fagan; Jennifer L. Heldmann; Rick C. Elphic; David J. Lawrence; Timothy J. Parker; Harrison H. Schmitt (Planetary and Space Science, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Prediction of Drug-Drug Interactions for Highly Plasma Protein Bound Compounds - David Tess; Makayla Harrison; Jian Lin; Rui Li; Li Di (The AAPS Journal, 2024)

PM10-bound trace elements in pan-European urban atmosphere - Xiansheng Liu; Xun Zhang; Tao Wang; Bowen Jin; Lijie Wu; Rosa Lara; Marta Monge; Cristina Reche; Jean-Luc Jaffrezo; Gaelle Uzu; Pamela Dominutti; Sophie Darfeuil; et al. (Environmental Research, 2024)

Agrochemical inputs to managed oil palm plantations are a probable risk to ecosystems: Results from a screening level risk assessment - Eleanor Dearlove; Sam Harrison; Claus Svendsen; David Spurgeon (Environmental Pollution, 2024)

Genome-wide study of gene-by-sex interactions identifies risks for cleft palate - Kelsey Robinson; Randy Parrish; Wasiu Lanre Adeyemo; Terri H. Beaty; Azeez Butali; Carmen J. Buxó; Lord J. J. Gowans; Jacqueline T. Hecht; Lina Moreno Uribe; Jeffrey C. Murray; Gary M. Shaw; Seth M. Weinberg; et al. (Human Genetics, 2024)

Comparing levoglucosan and mannosan ratios in sediments and corresponding aerosols from recent Australian fires - Harrison Stevens; Leon A. Barmuta; Zanna Chase; Krystyna M. Saunders; Atun Zawadzki; Andrew R. Bowie; Morgane M.G. Perron; Estrella Sanz Rodriguez; Brett Paull; David P. Child; Michael A.C. Hotchkis; Bernadette C. Proemse (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

A framework for optimising opportunistic collaborative syntheses to propel ecological conservation - Ana M.M. Sequeira; Amanda E. Bates; Graeme Hays; David W. Sims; Samantha Andrzejaczek; Asta Audzijonyte; Julia K. Baum; Martin Beal; Barbara Block; Joshua Cinner; Kaitlyn Cowley; Eric Gilman; et al. (Biological Conservation, 2024)

Barramundi ( Lates calcarifer ) rare coloration patterns: a multiomics approach to understand the “panda” phenotype - Roberta Marcoli; David B. Jones; Cecile Massault; Paul J. Harrison; Holly S. Cate; Dean R. Jerry (Journal of Fish Biology, 2024)
The barramundi ( Lates calcarifer ), a significant aquaculture species, typically displays silver to bronze coloration. However, attention is now drawn to rare variants like the “panda” phenotype, characterized by blotch‐like patterns of black (PB) and golden (PG) patches. This phenotype presents an opportunity to explore the molecular mechanisms underlying color variations in teleosts. Unlike stable color patterns in many fish, the “panda” variant demonstrates phenotypic plasticity, responding dynamically to unknown cues. We propose a complex interplay of genetic factors and epigenetic modifications, focusing on DNA methylation. Through a multiomics approach, we analyze transcriptomic and methylation patterns between PB and PG patches. Our study reveals differential gene expression related to melanosome trafficking and chromatophore differentiation. Although the specific gene responsible for the PB–PG difference remains elusive, candidate genes like asip1 , asip2 , mlph , and mreg have been identified. Methylation emerges as a potential contributor to the “panda” phenotype, with changes in gene promoters like hand2 and dynamin possibly influencing coloration. This research lays the groundwork for further exploration into rare barramundi color patterns, enhancing our understanding of color diversity in teleosts. Additionally, it underscores the “panda” phenotype's potential as a model for studying adult skin coloration.

Measurements of particulate methanesulfonic acid above the remote Arctic Ocean using a high resolution aerosol mass spectrometer - Yangmei Zhang; Junying Sun; Xiaojing Shen; Vipul Lal Chandani; Mao Du; Congbo Song; Yuqing Dai; Guoyuan Hu; Mingxi Yang; Gavin H. Tilstone; Tom Jordan; Giorgio Dall’Olmo; et al. (Atmospheric Environment, 2024)

Correction to: Lifespan effects in male UM‑HET3 mice treated with sodium thiosulfate, 16‑hydroxyestriol, and late‑start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Nisi Jiang; Catherine C. Kaczorowski; Navasuja Kumar; et al. (GeroScience, 2024)

Twenty-first century marine climate projections for the NW European shelf seas based on a perturbed parameter ensemble - Jonathan Tinker; Matthew D. Palmer; Benjamin J. Harrison; Enda O'Dea; David M. H. Sexton; Kuniko Yamazaki; John W. Rostron (Ocean Science, 2024)
The northwest European shelf (NWS) seas are environmentally and economically important, and an understanding of how their climate may change helps with their management. However, as the NWS seas are poorly represented in global climate models, a common approach is to dynamically downscale with an appropriate shelf sea model. We develop a set of physical marine climate projections for the NWS. We dynamically downscale 12 members of the HadGEM3-GC3.05 perturbed parameter ensemble (approximately 70 km horizontal resolution over Europe), developed for UKCP18, using the shelf sea model NEMO CO9 (7 km horizontal resolution). These are run under the RCP8.5 high-greenhouse-gas-emission scenario as continuous simulations over the period 1990–2098. We evaluate the simulations against observations in terms of tides, sea surface temperature (SST), surface and near-bed temperature and salinity, and sea surface height. These simulations represent the state of the art for NWS marine projections. We project an SST rise of 3.11 °C (± 2σ = 0.98 °C) and a sea surface salinity (SSS) freshening of −1.01 (± 2σ = 0.93; on the (unitless) practical salinity scale) for 2079–2098 relative to 2000–2019, averaged over the NWS (approximately bounded by the 200 m isobar and excluding the Norwegian Trench, the Skagerrak and Kattegat), a substantial seasonal stratification increase (23 d over the NWS seas), and a general weakening of the NWS residual circulation. While the patterns of NWS changes are similar to our previous projections, there is a greater warming and freshening that could reflect the change from the A1B emissions scenario to the RCP8.5 concentrations pathway or the higher climate sensitivity exhibited by HadGEM3-GC3.05. Off the shelf, south of Iceland, there is limited warming, consistent with a reduction in the Atlantic Meridional Overturning Circulation and associated northward heat transport. These projections have been publicly released, along with a consistent 200-year present-day control simulation, to provide an evidence base for climate change assessments and to facilitate climate impact studies. For example, we illustrate how the two products can be used to estimate climate trends, unforced variability and the time of emergence (ToE) of the climate signals. We calculate the average NWS SST ToE to be 2034 (with an 8-year range) and 2046 (with a 33-year range) for SSS. We also discuss how these projections can be used to describe NWS conditions under 2 and 4 °C global mean warming (compared with 1850–1900), as a policy-relevant exemplar use case.

Accelerator mass spectrometry measurements of 233U in groundwater, soil and vegetation at a legacy radioactive waste site - Timothy E. Payne; Jennifer J. Harrison; David P. Child; Stuart Hankin; Michael A.C. Hotchkis; Catherine E. Hughes; Mathew P. Johansen; Sangeeth Thiruvoth; Kerry L. Wilsher (Chemosphere, 2024)

Occurrence and mobility of thiolated arsenic in legacy mine tailings - Jaabir D. Ali; Adriana Guatame-Garcia; Heather E. Jamieson; Michael B. Parsons; Matthew I. Leybourne; Iris Koch; Kela P. Weber; David J. Patch; Anna L. Harrison; Bas Vriens (Science of The Total Environment, 2024)

Lifespan effects in male UM-HET3 mice treated with sodium thiosulfate, 16-hydroxyestriol, and late-start canagliflozin - Richard A. Miller; David E. Harrison; Gino A. Cortopassi; Ishmael Dehghan; Elizabeth Fernandez; Michael Garratt; John G. Geisler; Brett C. Ginsburg; Melissa L. Han; Catherine C. Kaczorowski; Navasuja Kumar; Scott F. Leiser; et al. (GeroScience, 2024)

Parameterization of nutrients and sediment build-up/wash-off processes for simulating stormwater quality from specific land uses - Mina Shahed Behrouz; David J. Sample; Odhiambo B. Kisila; Michael Harrison; Mohammad Nayeb Yazdi; Roja Kaveh Garna (Journal of Environmental Management, 2024)

Symbiodiniaceae diversity varies by host and environment across thermally distinct reefs - Magena R. Marzonie; Matthew R. Nitschke; Line K. Bay; David G. Bourne; Hugo B. Harrison (Molecular Ecology, 2024)
Endosymbiotic dinoflagellates (Symbiodiniaceae) influence coral thermal tolerance at both local and regional scales. In isolation, the effects of host genetics, environment, and thermal disturbances on symbiont communities are well understood, yet their combined effects remain poorly resolved. Here, we investigate Symbiodiniaceae across 1300 km in Australia's Coral Sea Marine Park to disentangle these interactive effects. We identified Symbiodiniaceae to species‐level resolution for three coral species ( Acropora cf humilis, Pocillopora verrucosa , and Pocillopora meandrina ) by sequencing two genetic markers of the symbiont (ITS2 and psbA ncr ), paired with genotype‐by‐sequencing of the coral host (DArT‐seq). Our samples predominantly returned sequences from the genus Cladocopium , where Acropora cf humilis affiliated with C3k, Pocillopora verrucosa with C. pacificum , and Pocillopora meandrina with C. latusorum . Multivariate analyses revealed that Acropora symbionts were driven strongly by local environment and thermal disturbances. In contrast, Pocillopora symbiont communities were both partitioned 2.5‐fold more by host genetic structure than by environmental structure. Among the two Pocillopora species, the effects of environment and host genetics explained four times more variation in symbionts for P. meandrina than P. verrucosa. The concurrent bleaching event in 2020 had variable impacts on symbiont communities, consistent with patterns in P. verrucosa and A. cf humilis , but not P. meandrina . Our findings demonstrate how symbiont macroscale community structure responses to environmental gradients depend on host species and their respective population structure. Integrating host, symbiont, and environmental data will help forecast the adaptive potential of corals and their symbionts amidst a rapidly changing environment.

Dispersal patterns of sandfish (Holothuria scabra) larvae in Manus Province, Papua New Guinea - Peter Waldie; David A. Feary; Michael Bode; Manuai Matawai; Hugo B. Harrison; Michael L. Berumen; Chris Molai; Maunoa Karo; Richard J. Hamilton (Frontiers in Marine Science, 2024)
In many tropical nations, coastal communities seek to manage their sea cucumber fisheries by establishing locally managed marine areas on their traditional fishing grounds. These managed areas can protect spawning stocks, however the extent to which they help to replenish nearby sea cucumber fisheries is debated, as nothing is known about the scales at which sea cucumber larvae disperse. In this study, we used genetic parentage analyses and statistical modelling to provide the first empirical measure of larval dispersal patterns for a sea cucumber species. We analysed tissue samples from 765 adult and 827 juvenile sandfish ( Holothuria scabra ) collected from five traditional fishing grounds of the Titan tribe, from Manus Province, Papua New Guinea. All adults were sampled from the Pere fishing grounds (the larval source area), with juveniles sampled from the Pere, Mbunai, Tawi, Timonai and Mbuke fishing grounds. Parentage analysis identified 15 juveniles that were the offspring of parents sampled from Pere fishing grounds, with six of these juveniles located in the same fishing grounds as their parents. The best-fit larval dispersal kernel predicted that the average H. scabra larvae travelled 15 km from its spawning location, with 50% of larvae settling within 6.7 km of their parents and 95% of larvae settling within 59 km of their parents. These results suggest that the Titan tribes’ desire to protect their H. scabra spawning stocks by establishing a network of locally managed marine areas across 65 km of continuous coastline is a culturally appropriate strategy, which has merit from both an ecological and fisheries standpoint.

On-orbit calibration and performance of the EMIT imaging spectrometer - David R. Thompson; Robert O. Green; Christine Bradley; Philip G. Brodrick; Natalie Mahowald; Eyal Ben Dor; Matthew Bennett; Michael Bernas; Nimrod Carmon; K. Dana Chadwick; Roger N. Clark; Red Willow Coleman; et al. (Remote Sensing of Environment, 2024)

Astaxanthin and meclizine extend lifespan in UM-HET3 male mice; fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate do not significantly affect lifespan in either sex at the doses and schedules used - David E. Harrison; Randy Strong; Peter Reifsnyder; Nadia Rosenthal; Ron Korstanje; Elizabeth Fernandez; Kevin Flurkey; Brett C. Ginsburg; Meredith D. Murrell; Martin A. Javors; Marisa Lopez-Cruzan; James F. Nelson; et al. (GeroScience, 2023)
In genetically heterogeneous (UM-HET3) mice produced by the CByB6F1 × C3D2F1 cross, the Nrf2 activator astaxanthin (Asta) extended the median male lifespan by 12% ( p = 0.003, log-rank test), while meclizine (Mec), an mTORC1 inhibitor, extended the male lifespan by 8% ( p = 0.03). Asta was fed at 1840 ± 520 (9) ppm and Mec at 544 ± 48 (9) ppm, stated as mean ± SE ( n ) of independent diet preparations. Both were started at 12 months of age. The 90th percentile lifespan for both treatments was extended in absolute value by 6% in males, but neither was significant by the Wang–Allison test. Five other new agents were also tested as follows: fisetin, SG1002 (hydrogen sulfide donor), dimethyl fumarate, mycophenolic acid, and 4-phenylbutyrate. None of these increased lifespan significantly at the dose and method of administration tested in either sex. Amounts of dimethyl fumarate in the diet averaged 35% of the target dose, which may explain the absence of lifespan effects. Body weight was not significantly affected in males by any of the test agents. Late life weights were lower in females fed Asta and Mec, but lifespan was not significantly affected in these females. The male-specific lifespan benefits from Asta and Mec may provide insights into sex-specific aspects of aging.

Tidal and circadian patterns of European eel during their spawning migration in the North Sea and the English Channel - Pieterjan Verhelst; Håkan Westerberg; Johan Coeck; Lianne Harrison; Tom Moens; Jan Reubens; Jeroen Van Wichelen; David Righton (Science of The Total Environment, 2023)

Grazing management for soil carbon in Australia: A review - Sarah E. McDonald; Warwick Badgery; Simon Clarendon; Susan Orgill; Katrina Sinclair; Rachelle Meyer; Dominique Bowen Butchart; Richard Eckard; David Rowlings; Peter Grace; Natalie Doran-Browne; Steven Harden; et al. (Journal of Environmental Management, 2023)

Early Eocene Arctic volcanism from carbonate-metasomatized mantle - James M. D. Day; D. Graham Pearson; Bruce A. Kjarsgaard; Abigail K. Barker; Geoff M. Nowell; Nancy Joyce; David Lowry; Chiranjeeb Sarkar; Christopher Harrison (Contributions to Mineralogy and Petrology, 2023)
Melilitite, nephelinite, basanite, and alkali basalt, along with phonolite differentiates, form the Freemans Cove Complex (FCC) in the south-eastern extremity of Bathurst Island (Nunavut, Canada). New 40 Ar/ 39 Ar chronology indicates their emplacement between ~ 56 and ~ 54 million years ago within a localized extensional structure. Melilitites and nephelinites, along with phonolite differentiates, likely relate to the beginning and end phases of extension, whereas alkali basalts were emplaced during a main extensional episode at ~ 55 Ma. The melilitites, nephelinites, and alkali basalts show no strong evidence for significant assimilation of crust, in contrast to some phonolites. Partial melting occurred within both the garnet- and spinel-facies mantle and sampled sources with He, O, Nd, Hf, and Os isotope characteristics indicative of peridotite with two distinct components. The first, expressed in higher degree partial melts, represents a relatively depleted component (“A”; 3 He/ 4 He ~ 8 R A , ε Nd i ~ + 3 ε Hf i ~ + 7, γ Os i ~ 0). The second was an enriched component (“B” 3 He/ 4 He < 3 R A , ε Nd i < – 1 ε Hf i < + 3, γ Os i > + 70) sampled by the lowest degree partial melts and represents carbonate-metasomatized peridotite. Magmatism in the FCC shows that rifting extended from the Labrador Sea to Bathurst Island and reached a zenith at ~ 55 Ma, during the Eurekan orogeny. The incompatible trace-element abundances and isotopic signatures of FCC rocks indicate melt generation occurred at the base of relatively thin lithosphere at the margin of a thick craton, with no mantle plume influence. FCC melt compositions are distinct from other continental rift magmatic provinces worldwide, and their metasomatized mantle source was plausibly formed synchronously with emplacement of Cretaceous kimberlites. The FCC illustrates that the range of isotopic compositions preserved in continental rift magmas are likely to be dominated by temporal changes in the extent of partial melting, as well as by the timing and degree of metasomatism recorded in the underlying continental lithosphere.

Ambient air particulate total lung deposited surface area (LDSA) levels in urban Europe - Xiansheng Liu; Hadiatullah Hadiatullah; Xun Zhang; Pedro Trechera; Marjan Savadkoohi; Meritxell Garcia-Marlès; Cristina Reche; Noemí Pérez; David C.S. Beddows; Imre Salma; Wanda Thén; Panayiotis Kalkavouras; et al. (Science of The Total Environment, 2023)

Shedding off-the-grid: The role of garment manufacturing and textile care in global microfibre pollution - Thomas Stanton; Elyse Stanes; Claire Gwinnett; Xiaoyu Lei; Myrna Cauilan-Cureg; Myrna Ramos; J. Brett Sallach; Eleanor Harrison; Amy Osborne; Catherine H. Sanders; Edwin Baynes; Antonia Law; et al. (Journal of Cleaner Production, 2023)

Insights for restoration: Reconstructing the drivers of long-term local fire events and vegetation turnover of a tropical peatland in Central Kalimantan - Khairun Nisha Mohamed Ramdzan; Patrick T. Moss; Geraldine Jacobsen; Angela Gallego-Sala; Dan Charman; Mark E. Harrison; Susan Page; Shailendra Mishra; David A. Wardle; Adi Jaya; Aswandi; Darmae Nasir; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Correction to: Developments in the classification and nomenclature of arthropod-infecting large DNA viruses that contain pif genes - Monique M. van Oers; Elisabeth A. Herniou; Johannes A. Jehle; Peter J. Krell; Adly M. M. Abd-Alla; Bergmann M. Ribeiro; David A. Theilmann; Zhihong Hu; Robert L. Harrison (Archives of Virology, 2023)

Demystifying global climate models for use in the life sciences - David S. Schoeman; Alex Sen Gupta; Cheryl S. Harrison; Jason D. Everett; Isaac Brito-Morales; Lee Hannah; Laurent Bopp; Patrick R. Roehrdanz; Anthony J. Richardson (Trends in Ecology & Evolution, 2023)

Measurement of road traffic brake and tyre dust emissions using both particle composition and size distribution data - David C.S. Beddows; Roy M. Harrison; Tomasz Gonet; Barbara A. Maher; Nicholas Odling (Environmental Pollution, 2023)

A decade of nature: Evolving approaches to Melbourne’s ‘nature in the city’ - Judy Bush; Cathy Oke; Ariana Dickey; Jacinta Humphrey; Lee Harrison; Marco Amati; Giorgia Fornari; Kylie Soanes; David Callow; Rodney Van der Ree (Landscape and Urban Planning, 2023)

Developments in the classification and nomenclature of arthropod-infecting large DNA viruses that contain pif genes - Monique M. van Oers; Elisabeth A. Herniou; Johannes A. Jehle; Peter J. Krell; Adly M.M. Abd-Alla; Bergmann M. Ribeiro; David A. Theilmann; Zhihong Hu; Robert L. Harrison (Archives of Virology, 2023)
Viruses of four families of arthropod-specific, large dsDNA viruses (the nuclear arthropod large DNA viruses, or NALDVs) possess homologs of genes encoding conserved components involved in the baculovirus primary infection mechanism. The presence of such homologs encoding per os infectivity factors ( pif genes), along with their absence from other viruses and the occurrence of other shared characteristics, suggests a common origin for the viruses of these families. Therefore, the class Naldaviricetes was recently established, accommodating these four families. In addition, within this class, the ICTV approved the creation of the order Lefavirales for three of these families, whose members carry homologs of the baculovirus genes that code for components of the viral RNA polymerase, which is responsible for late gene expression. We further established a system for the binomial naming of all virus species in the order Lefavirales , in accordance with a decision by the ICTV in 2019 to move towards a standardized nomenclature for all virus species. The binomial species names for members of the order Lefavirales consist of the name of the genus to which the species belongs (e.g., Alphabaculovirus ), followed by a single epithet that refers to the host species from which the virus was originally isolated. The common names of viruses and the abbreviations thereof will not change, as the format of virus names lies outside the remit of the ICTV.

Evolutionary dynamics and adaptive benefits of deleterious mutations in crop gene pools - Sangam L. Dwivedi; Pat Heslop-Harrison; Charles Spillane; Peter C. McKeown; David Edwards; Irwin Goldman; Rodomiro Ortiz (Trends in Plant Science, 2023)

Long-term effects of canagliflozin treatment on the skeleton of aged UM-HET3 mice - Gozde Yildirim; Edmara T. P. Bergamo; Sher Bahadur Poudel; Ryan R. Ruff; Manisha Dixit; Bin Hu; Dindo Q. Mijares; Lukasz Witek; Carolyn Chlebek; David E. Harrison; Randy Strong; Richard A. Miller; et al. (GeroScience, 2023)

A framework for functional fish passage decision-making - Rebecca Dolson; R. Allen Curry; Philip M. Harrison; Gordon Yamazaki; Tommi Linnansaari; Mark MacNevin; David L. G. Noakes (Environmental Biology of Fishes, 2023)

Acute manganese exposure impairs glutamatergic function in a young mouse model of Alzheimer’s disease - Brittany D. Spitznagel; Rebecca A. Buchanan; David C. Consoli; Megan K. Thibert; Aaron B. Bowman; William P. Nobis; Fiona E. Harrison (NeuroToxicology, 2023)

Canagliflozin retards age-related lesions in heart, kidney, liver, and adrenal gland in genetically heterogenous male mice - Jessica M. Snyder; Kerriann M. Casey; Andrzej Galecki; David E. Harrison; Hashan Jayarathne; Navasuja Kumar; Francesca Macchiarini; Nadia Rosenthal; Marianna Sadagurski; Adam B. Salmon; Randy Strong; Richard A. Miller; et al. (GeroScience, 2023)
Canagliflozin (Cana), a clinically important anti-diabetes drug, leads to a 14% increase in median lifespan and a 9% increase in the 90th percentile age when given to genetically heterogeneous male mice from 7 months of age, but does not increase lifespan in female mice. A histopathological study was conducted on 22-month-old mice to see if Cana retarded diverse forms of age-dependent pathology. This agent was found to diminish incidence or severity, in male mice only, of cardiomyopathy, glomerulonephropathy, arteriosclerosis, hepatic microvesicular cytoplasmic vacuolation (lipidosis), and adrenal cortical neoplasms. Protection against atrophy of the exocrine pancreas was seen in both males and females. Thus, the extension of lifespan in Cana-treated male mice, which is likely to reflect host- or tumor-mediated delay in lethal neoplasms, is accompanied by parallel retardation of lesions, in multiple tissues, that seldom if ever lead to death in these mice. Canagliflozin thus can be considered a drug that acts to slow the aging process and should be evaluated for potential protective effects against many other late-life conditions.

The effects of marine heatwaves on acute heat tolerance in corals - Magena R. Marzonie; Line K. Bay; David G. Bourne; Andrew S. Hoey; Samuel Matthews; Josephine J. V. Nielsen; Hugo B. Harrison (Global Change Biology, 2023)
Scleractinian coral populations are increasingly exposed to conditions above their upper thermal limits due to marine heatwaves, contributing to global declines of coral reef ecosystem health. However, historic mass bleaching events indicate there is considerable inter‐ and intra‐specific variation in thermal tolerance whereby species, individual coral colonies and populations show differential susceptibility to exposure to elevated temperatures. Despite this, we lack a clear understanding of how heat tolerance varies across large contemporary and historical environmental gradients, or the selective pressures that underpin this variation. Here we conducted standardised acute heat stress experiments to identify variation in heat tolerance among species and isolated reefs spanning a large environmental gradient across the Coral Sea Marine Park. We quantified the photochemical yield ( F v /F m ) of coral samples in three coral species, Acropora cf humilis , Pocillopora meandrina , and Pocillopora verrucosa , following exposure to four temperature treatments (local ambient temperatures, and + 3°C, +6°C and + 9°C above local maximum monthly mean). We quantified the temperature at which F v /F m decreased by 50% (termed ED50) and used derived values to directly compare acute heat tolerance across reefs and species. The ED50 for Acropora was 0.4–0.7°C lower than either Pocillopora species, with a 0.3°C difference between the two Pocillopora species. We also recorded 0.9°C to 1.9°C phenotypic variation in heat tolerance among reefs within species, indicating spatial heterogeneity in heat tolerance across broad environmental gradients. Acute heat tolerance had a strong positive relationship to mild heatwave exposure over the past 35 years (since 1986) but was negatively related to recent severe heatwaves (2016–2020). Phenotypic variation associated with mild thermal history in local environments provides supportive evidence that marine heatwaves are selecting for tolerant individuals and populations; however, this adaptive potential may be compromised by the exposure to recent severe heatwaves.

Sea Ice Microbiota in the Antarctic Peninsula Modulates Cloud-Relevant Sea Spray Aerosol Production - Manuel Dall’Osto; Dolors Vaqué; Ana Sotomayor-Garcia; Miguel Cabrera-Brufau; Marta Estrada; Teresa Buchaca; Montserrat Soler; Sdena Nunes; Sebastian Zeppenfeld; Manuela van Pinxteren; Hartmut Herrmann; Heike Wex; et al. (Frontiers in Marine Science, 2022)
Sea spray aerosol (SSA) formation plays a major role in the climate system. The Antarctic Peninsula (AP) is affected by the greatest warming occurring in the Southern Ocean; changes in cryospheric and biological processes are being observed. Whilst there is some evidence that organic material produced by ice algae and/or phytoplankton in the high Arctic contributes to SSA, less is known about Antarctic Sea ice (sympagic) regions. To gain insight into the influence of Antarctic Sea ice biology and biogeochemistry on atmospheric aerosol, we report simultaneous water-air measurements made by means of in situ aerosol chamber experiments. For the first time, we present a methodology showing that the controlled plunging jet aerosol chamber settings do not cause major cell disruption on the studied sea ice ecosystems. Larger sea ice phytoplankton cells (>20 µm; mainly diatoms) tend to sediment at the bottom of the chamber (during the 24h experiment) and likely have a minor role on SSA production. When comparing four chamber experiments - we find that the two producing more SSA are the ones with highest abundance of nanophytoplankton cells (<20 µm; mainly nanoflagellates) as well as viruses. Our marine biogeochemical data show two broad groups of dissolved organic carbon: one rich in carbohydrates and proteic material and one rich in humic-like substances; the latter enhancing SSA production. This work provides unique insights into sea ice productivity that modulates SSA production, with potentially significant climate impacts. Further studies of these types are advised in order to see how microbiology impacts the biogeochemical cycling of elements and how aerosols are formed and processed in cold regions.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Influence of offshore oil and gas structures on seascape ecological connectivity - Dianne L. McLean; Luciana C. Ferreira; Jessica A. Benthuysen; Karen J. Miller; Marie‐Lise Schläppy; Matthew J. Ajemian; Oliver Berry; Silvana N. R. Birchenough; Todd Bond; Fabio Boschetti; Ann S. Bull; Jeremy T. Claisse; et al. (Global Change Biology, 2022)
Offshore platforms, subsea pipelines, wells and related fixed structures supporting the oil and gas (O&G) industry are prevalent in oceans across the globe, with many approaching the end of their operational life and requiring decommissioning. Although structures can possess high ecological diversity and productivity, information on how they interact with broader ecological processes remains unclear. Here, we review the current state of knowledge on the role of O&G infrastructure in maintaining, altering or enhancing ecological connectivity with natural marine habitats. There is a paucity of studies on the subject with only 33 papers specifically targeting connectivity and O&G structures, although other studies provide important related information. Evidence for O&G structures facilitating vertical and horizontal seascape connectivity exists for larvae and mobile adult invertebrates, fish and megafauna; including threatened and commercially important species. The degree to which these structures represent a beneficial or detrimental net impact remains unclear, is complex and ultimately needs more research to determine the extent to which natural connectivity networks are conserved, enhanced or disrupted. We discuss the potential impacts of different decommissioning approaches on seascape connectivity and identify, through expert elicitation, critical knowledge gaps that, if addressed, may further inform decision making for the life cycle of O&G infrastructure, with relevance for other industries (e.g. renewables). The most highly ranked critical knowledge gap was a need to understand how O&G structures modify and influence the movement patterns of mobile species and dispersal stages of sessile marine species. Understanding how different decommissioning options affect species survival and movement was also highly ranked, as was understanding the extent to which O&G structures contribute to extending species distributions by providing rest stops, foraging habitat, and stepping stones. These questions could be addressed with further dedicated studies of animal movement in relation to structures using telemetry, molecular techniques and movement models. Our review and these priority questions provide a roadmap for advancing research needed to support evidence‐based decision making for decommissioning O&G infrastructure.

Evaporative misters for urban cooling and comfort: effectiveness and motivations for use - Jennifer K. Vanos; Mary K. Wright; Alana Kaiser; Ariane Middel; Harrison Ambrose; David M. Hondula (International Journal of Biometeorology, 2022)

Next‐generation phylogeography resolves post‐glacial colonization patterns in a widespread carnivore, the red fox ( Vulpes vulpes ), in Europe - Allan D. McDevitt; Ilaria Coscia; Samuel S. Browett; Aritz Ruiz‐González; Mark J. Statham; Iwona Ruczyńska; Liam Roberts; Joanna Stojak; Alain C. Frantz; Karin Norén; Erik O. Ågren; Jane Learmount; et al. (Molecular Ecology, 2022)
Carnivores tend to exhibit a lack of (or less pronounced) genetic structure at continental scales in both a geographic and temporal sense and this can confound the identification of post‐glacial colonization patterns in this group. In this study we used genome‐wide data (using genotyping by sequencing [GBS]) to reconstruct the phylogeographic history of a widespread carnivore, the red fox ( Vulpes vulpes ), by investigating broad‐scale patterns of genomic variation, differentiation and admixture amongst contemporary populations in Europe. Using 15,003 single nucleotide polymorphisms (SNPs) from 524 individuals allowed us to identify the importance of refugial regions for the red fox in terms of endemism (e.g., Iberia). In addition, we tested multiple post‐glacial recolonization scenarios of previously glaciated regions during the Last Glacial Maximum using an Approximate Bayesian Computation (ABC) approach that were unresolved from previous studies. This allowed us to identify the role of admixture from multiple source population post‐Younger Dryas in the case of Scandinavia and ancient land‐bridges in the colonization of the British Isles. A natural colonization of Ireland was deemed more likely than an ancient human‐mediated introduction as has previously been proposed and potentially points to a larger mammalian community on the island in the early post‐glacial period. Using genome‐wide data has allowed us to tease apart broad‐scale patterns of structure and diversity in a widespread carnivore in Europe that was not evident from using more limited marker sets and provides a foundation for next‐generation phylogeographic studies in other non‐model species.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Hypoxia as a physiological cue and pathological stress for coral larvae - Rachel Alderdice; Mathieu Pernice; Anny Cárdenas; David J. Hughes; Peter L. Harrison; Nadine Boulotte; Katie Chartrand; Michael Kühl; David J. Suggett; Christian R. Voolstra (Molecular Ecology, 2022)
Ocean deoxygenation events are intensifying worldwide and can rapidly drive adult corals into a state of metabolic crisis and bleaching‐induced mortality, but whether coral larvae are subject to similar stress remains untested. We experimentally exposed apo‐symbiotic coral larvae of Acropora selago to deoxygenation stress with subsequent reoxygenation aligned to their night‐day light cycle, and followed their gene expression using RNA‐Seq. After 12 h of deoxygenation stress (~2 mg O 2 /L), coral planulae demonstrated a low expression of HIF‐targeted hypoxia response genes concomitant with a significantly high expression of PHD2 (a promoter of HIFα proteasomal degradation), similar to corresponding adult corals. Despite exhibiting a consistent swimming phenotype compared to control samples, the differential gene expression observed in planulae exposed to deoxygenation‐reoxygenation suggests a disruption of pathways involved in developmental regulation, mitochondrial activity, lipid metabolism, and O 2 ‐sensitive epigenetic regulators. Importantly, we found that treated larvae exhibited a disruption in the expression of conserved HIF‐targeted developmental regulators, for example, Homeobox ( HOX ) genes, corroborating how changes in external oxygen levels can affect animal development. We discuss how the observed deoxygenation responses may be indicative of a possible acclimation response or alternatively may imply negative latent impacts for coral larval fitness.

Conservation resource allocation, small population resiliency, and the fallacy of conservation triage - David A. Wiedenfeld; Allison C. Alberts; Ariadne Angulo; Elizabeth L. Bennett; Onnie Byers; Topiltzin Contreras‐MacBeath; Gláucia Drummond; Gustavo A. B. da Fonseca; Claude Gascon; Ian Harrison; Nicolas Heard; Axel Hochkirch; et al. (Conservation Biology, 2021)
Some conservation prioritization methods are based on the assumption that conservation needs overwhelm current resources and not all species can be conserved; therefore, a conservation triage scheme (i.e., when the system is overwhelmed, species should be divided into three groups based on likelihood of survival, and efforts should be focused on those species in the group with the best survival prospects and reduced or denied to those in the group with no survival prospects and to those in the group not needing special efforts for their conservation) is necessary to guide resource allocation. We argue that this decision‐making strategy is not appropriate because resources are not as limited as often assumed, and it is not evident that there are species that cannot be conserved. Small population size alone, for example, does not doom a species to extinction; plants, reptiles, birds, and mammals offer examples. Although resources dedicated to conserving all threatened species are insufficient at present, the world's economic resources are vast, and greater resources could be dedicated toward species conservation. The political framework for species conservation has improved, with initiatives such as the UN Sustainable Development Goals and other international agreements, funding mechanisms such as The Global Environment Facility, and the rise of many nongovernmental organizations with nimble, rapid‐response small grants programs. For a prioritization system to allow no extinctions, zero extinctions must be an explicit goal of the system. Extinction is not inevitable, and should not be acceptable. A goal of no human‐induced extinctions is imperative given the irreversibility of species loss.

Changes to virus taxonomy and to the International Code of Virus Classification and Nomenclature ratified by the International Committee on Taxonomy of Viruses (2021) - Peter J. Walker; Stuart G. Siddell; Elliot J. Lefkowitz; Arcady R. Mushegian; Evelien M. Adriaenssens; Poliane Alfenas-Zerbini; Andrew J. Davison; Donald M. Dempsey; Bas E. Dutilh; María Laura García; Balázs Harrach; Robert L. Harrison; et al. (Archives of Virology, 2021)

The global abundance of tree palms - Robert Muscarella; Thaise Emilio; Oliver L. Phillips; Simon L. Lewis; Ferry Slik; William J. Baker; Thomas L. P. Couvreur; Wolf L. Eiserhardt; Jens‐Christian Svenning; Kofi Affum‐Baffoe; Shin‐Ichiro Aiba; Everton C. de Almeida; et al. (Global Ecology and Biogeography, 2020)
Aim Palms are an iconic, diverse and often abundant component of tropical ecosystems that provide many ecosystem services. Being monocots, tree palms are evolutionarily, morphologically and physiologically distinct from other trees, and these differences have important consequences for ecosystem services (e.g., carbon sequestration and storage) and in terms of responses to climate change. We quantified global patterns of tree palm relative abundance to help improve understanding of tropical forests and reduce uncertainty about these ecosystems under climate change. Location Tropical and subtropical moist forests. Time period Current. Major taxa studied Palms (Arecaceae). Methods We assembled a pantropical dataset of 2,548 forest plots (covering 1,191 ha) and quantified tree palm (i.e., ≥10 cm diameter at breast height) abundance relative to co‐occurring non‐palm trees. We compared the relative abundance of tree palms across biogeographical realms and tested for associations with palaeoclimate stability, current climate, edaphic conditions and metrics of forest structure. Results On average, the relative abundance of tree palms was more than five times larger between Neotropical locations and other biogeographical realms. Tree palms were absent in most locations outside the Neotropics but present in >80% of Neotropical locations. The relative abundance of tree palms was more strongly associated with local conditions (e.g., higher mean annual precipitation, lower soil fertility, shallower water table and lower plot mean wood density) than metrics of long‐term climate stability. Life‐form diversity also influenced the patterns; palm assemblages outside the Neotropics comprise many non‐tree (e.g., climbing) palms. Finally, we show that tree palms can influence estimates of above‐ground biomass, but the magnitude and direction of the effect require additional work. Conclusions Tree palms are not only quintessentially tropical, but they are also overwhelmingly Neotropical. Future work to understand the contributions of tree palms to biomass estimates and carbon cycling will be particularly crucial in Neotropical forests.

Effects of body size on estimation of mammalian area requirements - Michael J. Noonan; Christen H. Fleming; Marlee A. Tucker; Roland Kays; Autumn‐Lynn Harrison; Margaret C. Crofoot; Briana Abrahms; Susan C. Alberts; Abdullahi H. Ali; Jeanne Altmann; Pamela Castro Antunes; Nina Attias; et al. (Conservation Biology, 2020)
Accurately quantifying species’ area requirements is a prerequisite for effective area‐based conservation. This typically involves collecting tracking data on species of interest and then conducting home‐range analyses. Problematically, autocorrelation in tracking data can result in space needs being severely underestimated. Based on the previous work, we hypothesized the magnitude of underestimation varies with body mass, a relationship that could have serious conservation implications. To evaluate this hypothesis for terrestrial mammals, we estimated home‐range areas with global positioning system (GPS) locations from 757 individuals across 61 globally distributed mammalian species with body masses ranging from 0.4 to 4000 kg. We then applied block cross‐validation to quantify bias in empirical home‐range estimates. Area requirements of mammals 1, meaning the scaling of the relationship changed substantially at the upper end of the mass spectrum.

Systematic review and meta-analysis of the associations between body mass index, prostate cancer, advanced prostate cancer, and prostate-specific antigen - Sean Harrison; Kate Tilling; Emma L. Turner; Richard M. Martin; Rosie Lennon; J. Athene Lane; Jenny L. Donovan; Freddie C. Hamdy; David E. Neal; J. L. H. Ruud Bosch; Hayley E. Jones (Cancer Causes & Control, 2020)
Purpose The relationship between body mass index (BMI) and prostate cancer remains unclear. However, there is an inverse association between BMI and prostate-specific antigen (PSA), used for prostate cancer screening. We conducted this review to estimate the associations between BMI and (1) prostate cancer, (2) advanced prostate cancer, and (3) PSA. Methods We searched PubMed and Embase for studies until 02 October 2017 and obtained individual participant data from four studies. In total, 78 studies were identified for the association between BMI and prostate cancer, 21 for BMI and advanced prostate cancer, and 35 for BMI and PSA. We performed random-effects meta-analysis of linear associations of log-PSA and prostate cancer with BMI and, to examine potential non-linearity, of associations between categories of BMI and each outcome. Results In the meta-analyses with continuous BMI, a 5 kg/m 2 increase in BMI was associated with a percentage change in PSA of − 5.88% (95% CI − 6.87 to − 4.87). Using BMI categories, compared to normal weight men the PSA levels of overweight men were 3.43% lower (95% CI − 5.57 to − 1.23), and obese men were 12.9% lower (95% CI − 15.2 to − 10.7). Prostate cancer and advanced prostate cancer analyses showed little or no evidence associations. Conclusion There is little or no evidence of an association between BMI and risk of prostate cancer or advanced prostate cancer, and strong evidence of an inverse and non-linear association between BMI and PSA. The association between BMI and prostate cancer is likely biased if missed diagnoses are not considered.

A Flow Cytometric Method to Quantify the Endosomal Escape of a Protein Toxin to the Cytosol of Target Cells - Harrison J. Wensley; David A. Johnston; Wendy S. Smith; Suzanne E. Holmes; Sopsamorn U. Flavell; David J. Flavell (Pharmaceutical Research, 2020)
Purpose The aim of this work was to develop a quantitative, flow cytometric method for tracking the endolysosomal escape of a fluorescently labelled saporin toxin. Methods Flow cytometric measurements of fluorescent pulse width and height were used to track the endocytic uptake into Daudi cells of a fluorescently labelled saporin toxin and the saporin based immunotoxin, OKT10-SAP. Subsequently, measurement of changes in pulse width were used to investigate the effect of a triterpenoid saponin on the endolysosomal escape of internalised toxin into the cytosol. Live cell confocal microscopy was used to validate the flow cytometry data. Results Increased endolysosomal escape of saporin and OKT10-SAP was observed by confocal microscopy in cells treated with saponin. Fluorescent pulse width measurements were also able to detect and quantify escape more sensitively than confocal microscopy. Saponin induced endolysosomal escape could be abrogated by treatment with chloroquine, an inhibitor of endolysosomal acidification. Chloroquine abrogation of escape was also mirrored by a concomitant abrogation of cytotoxicity. Conclusions Poor endolysosomal escape is often a rate limiting step for the cytosolic delivery of protein toxins and other macromolecules. Pulse width analysis offers a simple method to semi-quantify the endolysosomal escape of this and similar molecules into the cytosol.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Production and characterisation of activated carbon and carbon nanotubes from potato peel waste and their application in heavy metal removal. - Ahmed I. Osman; Jacob Blewitt; Jehad K. Abu-Dahrieh; Charlie Farrell; Ala’a H. Al-Muhtaseb; John Harrison; David W. Rooney (Environmental Science and Pollution Research, 2019)
Herein, activated carbon (AC) and carbon nanotubes (CNTs) were synthesised from potato peel waste (PPW). Different ACs were synthesised via two activation steps: firstly, with phosphoric acid (designated PP) and then using potassium hydroxide (designated PK). The AC produced after the two activation steps showed a surface area as high as 833 m 2 g −1 with a pore volume of 0.44 cm 3 g −1 , where the raw material of PPW showed a surface area < 4 m 2 g −1 . This can help aid and facilitate the concept of the circular economy by effectively up-cycling and valorising waste lignocellulosic biomass such as potato peel waste to high surface area AC and subsequently, multi-walled carbon nanotubes (MWCNTs). Consequently, MWCNTs were prepared from the produced AC by mixing it with the nitrogen-based material melamine and iron precursor, iron (III) oxalate hexahydrate. This produced hydrophilic multi-wall carbon nanotubes (MWCNTs) with a water contact angle of θ = 14.97 °. Both AC and CNT materials were used in heavy metal removal (HMR) where the maximum lead absorption was observed for sample PK with a 84% removal capacity after the first hour of testing. This result signifies that the synthesis of these up-cycled materials can have applications in areas such as wastewater treatment or other conventional AC/CNT end uses with a rapid cycle time in a two-fold approach to improve the eco-friendly synthesis of such value-added products and the circular economy from a significant waste stream, i.e., PPW.

Uncertainty in geomorphological responses to climate change - Stephan Harrison; Tim Mighall; David A. Stainforth; Philip Allen; Mark Macklin; Edward Anderson; Jasper Knight; Dmitri Mauquoy; David Passmore; Brice Rea; Matteo Spagnolo; Sarah Shannon (Climatic Change, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Extreme heterogeneity of population response to climatic variation and the limits of prediction - Chris C. Nice; Matthew L. Forister; Joshua G. Harrison; Zachariah Gompert; James A. Fordyce; James H. Thorne; David P. Waetjen; Arthur M. Shapiro (Global Change Biology, 2019)
Certain general facets of biotic response to climate change, such as shifts in phenology and geographic distribution, are well characterized; however, it is not clear whether the observed similarity of responses across taxa will extend to variation in other population‐level processes. We examined population response to climatic variation using long‐term incidence data (collected over 42 years) encompassing 149 butterfly species and considerable habitat diversity (10 sites along an elevational gradient from sea level to over 2,700 m in California). Population responses were characterized by extreme heterogeneity that was not attributable to differences in species composition among sites. These results indicate that habitat heterogeneity might be a buffer against climate change and highlight important questions about mechanisms maintaining interpopulation differences in responses to weather. Despite overall heterogeneity of response, population dynamics were accurately predicted by our model for many species at each site. However, the overall correlation between observed and predicted incidence in a cross validation analysis was moderate (Pearson's r = 0.23, SE 0.01), and 97% of observed data fell within the predicted 95% credible intervals. Prediction was most successful for more abundant species as well as for sites with lower annual turnover. Population‐level heterogeneity in response to climate variation and the limits of our predictive power highlight the challenges for a future of increasing climatic variability.

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

The Be-Well Study: a prospective cohort study of lifestyle and genetic factors to reduce the risk of recurrence and progression of non-muscle-invasive bladder cancer - Marilyn L. Kwan; Lawrence H. Kushi; Kim N. Danforth; Janise M. Roh; Isaac J. Ergas; Valerie S. Lee; Kimberly L. Cannavale; Teresa N. Harrison; Richard Contreras; Ronald K. Loo; David S. Aaronson; Charles P. Quesenberry; et al. (Cancer Causes & Control, 2019)

The complete genome sequence of a second alphabaculovirus from the true armyworm, Mythimna unipuncta: implications for baculovirus phylogeny and host specificity - Robert L. Harrison; Joseph D. Mowery; Gary R. Bauchan; David A. Theilmann; Martin A. Erlandson (Virus Genes, 2019)

Late Quaternary meltwater pulses and sea level change - Stephan Harrison; David E. Smith; Neil F. Glasser (Journal of Quaternary Science, 2019)
After the Last Glacial Maximum (LGM) global mean sea level (GMSL) rise was characterized by rapid increases over short (decadal to centennial) timescales superimposed on a longer term secular rise and these have been termed meltwater pulses (MWPs). In this paper we review the timing, impact and nature of these and the effects of rapid drainage of large post‐glacial MWPs into the world's oceans. We identify nine MWPs, four of which occurred in three periods of rapid sea level rise (19.5–18.8, 14.8–13.0 and 11.5–11.1 ka BP ). The rest are dated to the period during the Early Holocene sea level rise after 11 ka BP . We show that drainage of the known post‐glacial lakes in total produced less than around 1.2 m of the 125 m of GMSLR since the LGM.

Livestock and livelihoods of smallholder cattle-owning households in Cambodia: the contribution of on-farm and off-farm activities to income and food security - Katherine Ashley; Holly Harrison; Phalleap Hok Chan; Suon Sothoeun; James Robert Young; Peter Andrew Windsor; Russell David Bush (Tropical Animal Health and Production, 2018)

Glacier protection laws: Potential conflicts in managing glacial hazards and adapting to climate change - Pablo Iribarren Anacona; Josie Kinney; Marius Schaefer; Stephan Harrison; Ryan Wilson; Alexis Segovia; Bruno Mazzorana; Felipe Guerra; David Farías; John M. Reynolds; Neil F. Glasser (Ambio, 2018)

Evaluating potential of green alga Chlorella vulgaris to accumulate phosphorus and to fertilize nutrient-poor soil substrates for crop plants - Christina Schreiber; Henning Schiedung; Lucy Harrison; Christoph Briese; Bärbel Ackermann; Josefine Kant; Silvia D. Schrey; Diana Hofmann; Dipali Singh; Oliver Ebenhöh; Wulf Amelung; Ulrich Schurr; et al. (Journal of Applied Phycology, 2018)

Neisseria meningitidis disease-associated clones in Amazonas State, Brazil - Luciete A. Silva; Beatriz Coronato; Jessica Schlackman; Jane W. Marsh; Chinelo Ezeonwuka; Andréia C. L. Fernandes; Victor C. Souza; Lirna S. da Silva; Elaine F. Q. de Amorim; Felipe G. Naveca; Bernardino C. de Albuquerque; Alcirene Amaral; et al. (Infectious Diseases, 2018)

Identification of powdery mildew resistance QTL in strawberry (Fragaria × ananassa) - Helen M. Cockerton; Robert J. Vickerstaff; Amanda Karlström; Fiona Wilson; Maria Sobczyk; Joe Q. He; Daniel J. Sargent; Andy J. Passey; Kirsty J. McLeary; Katalin Pakozdi; Nicola Harrison; Maria Lumbreras-Martinez; et al. (Theoretical and Applied Genetics, 2018)

Gene Editing of Stem Cells to Model and Treat Disease - Jennifer A. Hollywood; David J. Sanz; Alan J. Davidson; Patrick T. Harrison (Current Stem Cell Reports, 2018)

Effects of an Experimental Water-level Drawdown on Methane Emissions from a Eutrophic Reservoir - Jake J. Beaulieu; David A. Balz; M. Keith Birchfield; John A. Harrison; Christopher T. Nietch; Michelle C. Platz; William C. Squier; Sarah Waldo; John T. Walker; Karen M. White; Jade L. Young (Ecosystems, 2018)

Comparing human peritoneal fluid and phosphate-buffered saline for drug delivery: do we need bio-relevant media? - Prabhat Bhusal; Jamie Lee Rahiri; Bruce Sua; Jessica E. McDonald; Mahima Bansal; Sara Hanning; Manisha Sharma; Kaushik Chandramouli; Jeff Harrison; Georgina Procter; Gavin Andrews; David S. Jones; et al. (Drug Delivery and Translational Research, 2018)

What can conservation strategies learn from the ecosystem services approach? Insights from ecosystem assessments in two Spanish protected areas - Marina García-Llorente; Paula A. Harrison; Pam Berry; Ignacio Palomo; Erik Gómez-Baggethun; Irene Iniesta-Arandia; Carlos Montes; David García del Amo; Berta Martín-López (Biodiversity and Conservation, 2018)

Use of QSPR Modeling to Characterize In Vitro Binding of Drugs to a Gut-Restricted Polymer - Christine Taylor Brew; James F. Blake; Anita Mistry; Fengling Liu; Diana Carreno; Deidre Madsen; YongQi Mu; Martha Mayo; Wilhelm Stahl; David Matthews; Derek Maclean; Steve Harrison (Pharmaceutical Research, 2018)

The complete genome sequence of a third distinct baculovirus isolated from the true armyworm, Mythimna unipuncta, contains two copies of the lef-7 gene - Robert L. Harrison; Joseph D. Mowery; Daniel L. Rowley; Gary R. Bauchan; David A. Theilmann; George F. Rohrmann; Martin A. Erlandson (Virus Genes, 2018)

Widespread hybridization and bidirectional introgression in sympatric species of coral reef fish - Hugo B. Harrison; Michael L. Berumen; Pablo Saenz‐Agudelo; Eva Salas; David H. Williamson; Geoffrey P. Jones (Molecular Ecology, 2017)
Coral reefs are highly diverse ecosystems, where numerous closely related species often coexist. How new species arise and are maintained in these high geneflow environments have been long‐standing conundrums. Hybridization and patterns of introgression between sympatric species provide a unique insight into the mechanisms of speciation and the maintenance of species boundaries. In this study, we investigate the extent of hybridization between two closely related species of coral reef fish: the common coral trout ( Plectropomus leopardus ) and the bar‐cheek coral trout ( Plectropomus maculatus ). Using a complementary set of 25 microsatellite loci, we distinguish pure genotype classes from first‐ and later‐generation hybrids, identifying 124 interspecific hybrids from a collection of 2,991 coral trout sampled in inshore and mid‐shelf reefs of the southern Great Barrier Reef. Hybrids were ubiquitous among reefs, fertile and spanned multiple generations suggesting both ecological and evolutionary processes are acting to maintain species barriers. We elaborate on these finding to investigate the extent of genomic introgression and admixture from 2,271 SNP loci recovered from a dd RAD library of pure and hybrid individuals. An analysis of genomic clines on recovered loci indicates that 261 SNP loci deviate from a model of neutral introgression, of which 132 indicate a pattern of introgression consistent with selection favouring both hybrid and parental genotypes. Our findings indicate genome‐wide, bidirectional introgression between two sympatric species of coral reef fishes and provide further support to a growing body of evidence for the role of hybridization in the evolution of coral reef fishes.

Effects of Backpacker Use, Pack Stock Trail Use, and Pack Stock Grazing on Water-Quality Indicators, Including Nutrients, E. coli, Hormones, and Pharmaceuticals, in Yosemite National Park, USA - Harrison Forrester; David Clow; James Roche; Alan Heyvaert; William Battaglin (Environmental Management, 2017)

Shifting paradigms in restoration of the world's coral reefs - Madeleine J. H. van Oppen; Ruth D. Gates; Linda L. Blackall; Neal Cantin; Leela J. Chakravarti; Wing Y. Chan; Craig Cormick; Angela Crean; Katarina Damjanovic; Hannah Epstein; Peter L. Harrison; Thomas A. Jones; et al. (Global Change Biology, 2017)
Many ecosystems around the world are rapidly deteriorating due to both local and global pressures, and perhaps none so precipitously as coral reefs. Management of coral reefs through maintenance (e.g., marine‐protected areas, catchment management to improve water quality), restoration, as well as global and national governmental agreements to reduce greenhouse gas emissions (e.g., the 2015 Paris Agreement) is critical for the persistence of coral reefs. Despite these initiatives, the health and abundance of corals reefs are rapidly declining and other solutions will soon be required. We have recently discussed options for using assisted evolution (i.e., selective breeding, assisted gene flow, conditioning or epigenetic programming, and the manipulation of the coral microbiome) as a means to enhance environmental stress tolerance of corals and the success of coral reef restoration efforts. The 2014–2016 global coral bleaching event has sharpened the focus on such interventionist approaches. We highlight the necessity for consideration of alternative (e.g., hybrid) ecosystem states, discuss traits of resilient corals and coral reef ecosystems, and propose a decision tree for incorporating assisted evolution into restoration initiatives to enhance climate resilience of coral reefs.

The nature and consequences of cognitive deficits among tobacco smokers with HIV: a comparison to tobacco smokers without HIV - Joseph D. Harrison; Jessica A. Dochney; Sonja Blazekovic; Frank Leone; David Metzger; Ian Frank; Robert Gross; Anita Hole; Karam Mounzer; Steven Siegel; Robert A. Schnoll; Rebecca L. Ashare (Journal of NeuroVirology, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

Assessing uncertainties in land cover projections - Peter Alexander; Reinhard Prestele; Peter H. Verburg; Almut Arneth; Claudia Baranzelli; Filipe Batista e Silva; Calum Brown; Adam Butler; Katherine Calvin; Nicolas Dendoncker; Jonathan C. Doelman; Robert Dunford; et al. (Global Change Biology, 2017)
Understanding uncertainties in land cover projections is critical to investigating land‐based climate mitigation policies, assessing the potential of climate adaptation strategies and quantifying the impacts of land cover change on the climate system. Here, we identify and quantify uncertainties in global and European land cover projections over a diverse range of model types and scenarios, extending the analysis beyond the agro‐economic models included in previous comparisons. The results from 75 simulations over 18 models are analysed and show a large range in land cover area projections, with the highest variability occurring in future cropland areas. We demonstrate systematic differences in land cover areas associated with the characteristics of the modelling approach, which is at least as great as the differences attributed to the scenario variations. The results lead us to conclude that a higher degree of uncertainty exists in land use projections than currently included in climate or earth system projections. To account for land use uncertainty, it is recommended to use a diverse set of models and approaches when assessing the potential impacts of land cover change on future climate. Additionally, further work is needed to better understand the assumptions driving land use model results and reveal the causes of uncertainty in more depth, to help reduce model uncertainty and improve the projections of land cover.

Investigating the prostate specific antigen, body mass index and age relationship: is an age–BMI-adjusted PSA model clinically useful? - Sean Harrison; Kate Tilling; Emma L. Turner; J. Athene Lane; Andrew Simpkin; Michael Davis; Jenny Donovan; Freddie C. Hamdy; David E. Neal; Richard M. Martin (Cancer Causes & Control, 2016)

Large‐scale, multidirectional larval connectivity among coral reef fish populations in the Great Barrier Reef Marine Park - David H. Williamson; Hugo B. Harrison; Glenn R. Almany; Michael L. Berumen; Michael Bode; Mary C. Bonin; Severine Choukroun; Peter J. Doherty; Ashley J. Frisch; Pablo Saenz‐Agudelo; Geoffrey P. Jones (Molecular Ecology, 2016)
Larval dispersal is the key process by which populations of most marine fishes and invertebrates are connected and replenished. Advances in larval tagging and genetics have enhanced our capacity to track larval dispersal, assess scales of population connectivity, and quantify larval exchange among no‐take marine reserves and fished areas. Recent studies have found that reserves can be a significant source of recruits for populations up to 40 km away, but the scale and direction of larval connectivity across larger seascapes remain unknown. Here, we apply genetic parentage analysis to investigate larval dispersal patterns for two exploited coral reef groupers ( Plectropomus maculatus and Plectropomus leopardus ) within and among three clusters of reefs separated by 60–220 km within the Great Barrier Reef Marine Park, Australia. A total of 69 juvenile P. maculatus and 17 juvenile P. leopardus (representing 6% and 9% of the total juveniles sampled, respectively) were genetically assigned to parent individuals on reefs within the study area. We identified both short‐distance larval dispersal within regions (200 m to 50 km) and long‐distance, multidirectional dispersal of up to ~250 km among regions. Dispersal strength declined significantly with distance, with best‐fit dispersal kernels estimating median dispersal distances of ~110 km for P. maculatus and ~190 km for P. leopardus . Larval exchange among reefs demonstrates that established reserves form a highly connected network and contribute larvae for the replenishment of fished reefs at multiple spatial scales. Our findings highlight the potential for long‐distance dispersal in an important group of reef fishes, and provide further evidence that effectively protected reserves can yield recruitment and sustainability benefits for exploited fish populations.

Heritability of in vitro phenotypes exhibited by murine adipose-derived stromal cells - Zixuan Jiang; David E. Harrison; Makayla E. Parsons; Susan McClatchy; Lawrence Jacobs; Robert Pazdro (Mammalian Genome, 2016)

Controlled release drug delivery systems to improve post-operative pharmacotherapy - Prabhat Bhusal; Jeff Harrison; Manisha Sharma; David S. Jones; Andrew G. Hill; Darren Svirskis (Drug Delivery and Translational Research, 2016)

Estimating the extent and structure of trade in horticultural orchids via social media - Amy Hinsley; Tamsin E. Lee; Joseph R. Harrison; David L. Roberts (Conservation Biology, 2016)
The wildlife trade is a lucrative industry involving thousands of animal and plant species. The increasing use of the internet for both legal and illegal wildlife trade is well documented, but there is evidence that trade may be emerging on new online technologies such as social media. Using the orchid trade as a case study, we conducted the first systematic survey of wildlife trade on an international social‐media website. We focused on themed forums (groups), where people with similar interests can interact by uploading images or text (posts) that are visible to other group members. We used social‐network analysis to examine the ties between 150 of these orchid‐themed groups to determine the structure of the network. We found 4 communities of closely linked groups based around shared language. Most trade occurred in a community that consisted of English‐speaking and Southeast Asian groups. In addition to the network analysis, we randomly sampled 30 groups from the whole network to assess the prevalence of trade in cultivated and wild plants. Of 55,805 posts recorded over 12 weeks, 8.9% contained plants for sale, and 22–46% of these posts pertained to wild‐collected orchids. Although total numbers of posts about trade were relatively small, the large proportion of posts advertising wild orchids for sale supports calls for better monitoring of social media for trade in wild‐collected plants.

Impact of gene editing on the study of cystic fibrosis - Patrick T. Harrison; David J. Sanz; Jennifer A. Hollywood (Human Genetics, 2016)

Assessing the extent and nature of wildlife trade on the dark web - Joseph R. Harrison; David L. Roberts; Julio Hernandez‐Castro (Conservation Biology, 2016)
Use of the internet as a trade platform has resulted in a shift in the illegal wildlife trade. Increased scrutiny of illegal wildlife trade has led to concerns that online trade of wildlife will move onto the dark web. To provide a baseline of illegal wildlife trade on the dark web, we downloaded and archived 9852 items (individual posts) from the dark web, then searched these based on a list of 121 keywords associated with illegal online wildlife trade, including 30 keywords associated with illegally traded elephant ivory on the surface web. Results were compared with items known to be illegally traded on the dark web, specifically cannabis, cocaine, and heroin, to compare the extent of the trade. Of these 121 keywords, 4 resulted in hits, of which only one was potentially linked to illegal wildlife trade. This sole case was the sale and discussion of Echinopsis pachanoi (San Pedro cactus), which has hallucinogenic properties. This negligible level of activity related to the illegal trade of wildlife on the dark web relative to the open and increasing trade on the surface web may indicate a lack of successful enforcement against illegal wildlife trade on the surface web.

Understanding a migratory species in a changing world: climatic effects and demographic declines in the western monarch revealed by four decades of intensive monitoring - Anne E. Espeset; Joshua G. Harrison; Arthur M. Shapiro; Chris C. Nice; James H. Thorne; David P. Waetjen; James A. Fordyce; Matthew L. Forister (Oecologia, 2016)

Mentoring Strategies and Outcomes of Two Federally Funded Cancer Research Training Programs for Underrepresented Students in the Biomedical Sciences - Marvella E. Ford; Latecia M. Abraham; Anita L. Harrison; Melanie S. Jefferson; Tonya R. Hazelton; Heidi Varner; Kimberly Cannady; Carla S. Frichtel; Omar Bagasra; Leroy Davis; David E. Rivers; Sabra C. Slaughter; et al. (Journal of Cancer Education, 2016)

Dietary shift in juvenile coral trout (Plectropomus maculatus) following coral reef degradation from a flood plume disturbance - Colin K. C. Wen; Mary C. Bonin; Hugo B. Harrison; David H. Williamson; Geoffrey P. Jones (Coral Reefs, 2016)

The role of marine reserves in the replenishment of a locally impacted population of anemonefish on the Great Barrier Reef - Mary C. Bonin; Hugo B. Harrison; David H. Williamson; Ashley J. Frisch; Pablo Saenz‐Agudelo; Michael L. Berumen; Geoffrey P. Jones (Molecular Ecology, 2016)
The development of parentage analysis to track the dispersal of juvenile offspring has given us unprecedented insight into the population dynamics of coral reef fishes. These tools now have the potential to inform fisheries management and species conservation, particularly for small fragmented populations under threat from exploitation and disturbance. In this study, we resolve patterns of larval dispersal for a population of the anemonefish Amphiprion melanopus in the Keppel Islands (southern Great Barrier Reef). Habitat loss and fishing appear to have impacted this population and a network of no‐take marine reserves currently protects 75% of the potential breeders. Using parentage analysis, we estimate that 21% of recruitment in the island group was generated locally and that breeding adults living in reserves were responsible for 79% (31 of 39) of these of locally produced juveniles. Overall, the network of reserves was fully connected via larval dispersal; however, one reserve was identified as a critical source of larvae for the island group. The population in the Keppel Islands also appears to be well‐connected to other source populations at least 60 km away, given that 79% (145 of 184) of the juveniles sampled remained unassigned in the parentage analysis. We estimated the effective size of the A. melanopus metapopulation to be 745 (582–993 95% CI ) and recommend continued monitoring of its genetic status. Maintaining connectivity with populations beyond the Keppel Islands and recovery of local recruitment habitat, potentially through active restoration of host anemone populations, will be important for its long‐term persistence.

Design and validation of a qPCR assay for accurate detection and initial serogrouping of Legionella pneumophila in clinical specimens by the ESCMID Study Group for Legionella Infections (ESGLI) - M. Mentasti; D. Kese; F. Echahidi; S. A. Uldum; B. Afshar; S. David; J. Mrazek; R. De Mendonça; T. G. Harrison; V. J. Chalker (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

BioEarth: Envisioning and developing a new regional earth system model to inform natural and agricultural resource management - Jennifer C. Adam; Jennie C. Stephens; Serena H. Chung; Michael P. Brady; R. David Evans; Chad E. Kruger; Brian K. Lamb; Mingliang Liu; Claudio O. Stöckle; Joseph K. Vaughan; Kirti Rajagopalan; John A. Harrison; et al. (Climatic Change, 2015)

Patterns of peripheral neuropathy in ART-naïve patients initiating modern ART regimen - Anthony J. Lee; Ronald J. Bosch; Scott R. Evans; Kunling Wu; Taylor Harrison; Philip Grant; David B. Clifford (Journal of NeuroVirology, 2015)

Genetic structure, admixture and invasion success in a Holarctic defoliator, the gypsy moth ( Lymantria dispar , Lepidoptera: Erebidae) - Yunke Wu; John J. Molongoski; Deborah F. Winograd; Steven M. Bogdanowicz; Artemis S. Louyakis; David R. Lance; Victor C. Mastro; Richard G. Harrison (Molecular Ecology, 2015)
Characterizing the current population structure of potentially invasive species provides a critical context for identifying source populations and for understanding why invasions are successful. Non‐native populations inevitably lose genetic diversity during initial colonization events, but subsequent admixture among independently introduced lineages may increase both genetic variation and adaptive potential. Here we characterize the population structure of the gypsy moth ( L ymantria dispar L innaeus), one of the world's most destructive forest pests. Native to Eurasia and recently introduced to N orth A merica, the current distribution of gypsy moth includes forests throughout the temperate region of the northern hemisphere. Analyses of microsatellite loci and mitochondrial DNA sequences for 1738 individuals identified four genetic clusters within L . dispar . Three of these clusters correspond to the three named subspecies; N orth A merican populations represent a distinct fourth cluster, presumably a consequence of the population bottleneck and allele frequency change that accompanied introduction. We find no evidence that admixture has been an important catalyst of the successful invasion and range expansion in N orth A merica. However, we do find evidence of ongoing hybridization between subspecies and increased genetic variation in gypsy moth populations from E astern A sia, populations that now pose a threat of further human‐mediated introductions. Finally, we show that current patterns of variation can be explained in terms of climate and habitat changes during the P leistocene, a time when temperate forests expanded and contracted. Deeply diverged matrilines in E urope imply that gypsy moths have been there for a long time and are not recent arrivals from A sia.

An animal model mimicking pedunculopontine nucleus cholinergic degeneration in Parkinson’s disease - Ilse S. Pienaar; Ian F. Harrison; Joanna L. Elson; Alexander Bury; Petter Woll; Anna Katharina Simon; David T. Dexter (Brain Structure and Function, 2015)

Validation of microsatellite multiplexes for parentage analysis in a coral reef fish (Lutjanus carponotatus, Lutjanidae) - Hugo B. Harrison; Kevin A. Feldheim; Geoffrey P. Jones; Hicham Mansour; Sadhasivam Perumal; David H. Williamson; Michael L. Berumen (Conservation Genetics Resources, 2014)

Range‐wide multilocus phylogeography of the red fox reveals ancient continental divergence, minimal genomic exchange and distinct demographic histories - Mark J. Statham; James Murdoch; Jan Janecka; Keith B. Aubry; Ceiridwen J. Edwards; Carl D. Soulsbury; Oliver Berry; Zhenghuan Wang; David Harrison; Malcolm Pearch; Louise Tomsett; Judith Chupasko; et al. (Molecular Ecology, 2014)
Widely distributed taxa provide an opportunity to compare biogeographic responses to climatic fluctuations on multiple continents and to investigate speciation. We conducted the most geographically and genomically comprehensive study to date of the red fox ( Vulpes vulpes ), the world's most widely distributed wild terrestrial carnivore. Analyses of 697 bp of mitochondrial sequence in ~1000 individuals suggested an ancient Middle Eastern origin for all extant red foxes and a 400 kya ( SD = 139 kya) origin of the primary North American (Nearctic) clade. Demographic analyses indicated a major expansion in Eurasia during the last glaciation (~50 kya), coinciding with a previously described secondary transfer of a single matriline (Holarctic) to North America. In contrast, North American matrilines (including the transferred portion of Holarctic clade) exhibited no signatures of expansion until the end of the Pleistocene (~12 kya). Analyses of 11 autosomal loci from a subset of foxes supported the colonization time frame suggested by mt DNA (and the fossil record) but, in contrast, reflected no detectable secondary transfer, resulting in the most fundamental genomic division of red foxes at the Bering Strait. Endemic continental Y‐chromosome clades further supported this pattern. Thus, intercontinental genomic exchange was overall very limited, consistent with long‐term reproductive isolation since the initial colonization of North America. Based on continental divergence times in other carnivoran species pairs, our findings support a model of peripatric speciation and are consistent with the previous classification of the North American red fox as a distinct species, V. fulva .

Acute over-the-counter pharmacological intervention does not adversely affect behavioral outcome following diffuse traumatic brain injury in the mouse - Jordan L. Harrison; Rachel K. Rowe; Bruce F. O’Hara; P. David Adelson; Jonathan Lifshitz (Experimental Brain Research, 2014)

Remote Antarctic feeding ground important for east Australian humpback whales - Rochelle Constantine; Debbie Steel; Judy Allen; Megan Anderson; Olive Andrews; C. Scott Baker; Peta Beeman; Daniel Burns; Jean-Benoît Charrassin; Simon Childerhouse; Michael Double; Paul Ensor; et al. (Marine Biology, 2014)

Migratory movements of individual humpback whales photographed off the eastern coast of Australia - Daniel Burns; Lyndon Brooks; Peter Harrison; Trish Franklin; Wally Franklin; David Paton; Phil Clapham (Marine Mammal Science, 2014)
Humpback whales ( Megaptera novaeangliae ) migrate long distances each year on a return journey from low‐latitude breeding grounds to high‐latitude feeding grounds. Migration is influenced by subtle and complex social behaviors and the assumption that whales transit directly through the migratory corridor off the east coast of Australia requires further investigation. From 2003 to 2005, we followed the movements of 99 individual whales within one migratory cycle from three locations, off Byron Bay during the whales' northern migration and in Hervey Bay and at Ballina during the southern migration. The median sighting interval of whales between Byron Bay and Hervey Bay ( n = 26) was 52 d ( IQR = 42.5–75.5); between Byron Bay and Ballina ( n = 21) was 59 d ( IQR = 47.0–70.0); and between Hervey Bay and Ballina ( n = 33) was 9 d (8.0–14.0). The overall pattern observed from these resightings suggests that Group E1 humpback whales spend approximately two months in the northern quarter of their range during the austral winter months. Intraseason resightings of whales at Ballina ( n = 13, median sighting interval = 7 d) also suggest that some individuals, particularly adult males, may circle back north during their general southward journey along this part of the coast, perhaps in an attempt to increase mating opportunities.

Effects of Stock Use and Backpackers on Water Quality in Wilderness in Sequoia and Kings Canyon National Parks, USA - David W. Clow; Harrison Forrester; Benjamin Miller; Heidi Roop; James O. Sickman; Hodon Ryu; Jorge Santo Domingo (Environmental Management, 2013)

The extracellular matrix protects P seudomonas aeruginosa biofilms by limiting the penetration of tobramycin - Boo Shan Tseng; Wei Zhang; Joe J. Harrison; Tam P. Quach; Jisun Lee Song; Jon Penterman; Pradeep K. Singh; David L. Chopp; Aaron I. Packman; Matthew R. Parsek (Environmental Microbiology, 2013)
Summary Biofilm cells are less susceptible to antimicrobials than their planktonic counterparts. While this phenomenon is multifactorial, the ability of the matrix to reduce antibiotic penetration into the biofilm is thought to be of limited importance studies suggest that antibiotics move fairly rapidly through biofilms. In this study, we monitored the transport of two clinically relevant antibiotics, tobramycin and ciprofloxacin, into non‐mucoid P seudomonas aeruginosa biofilms. To our surprise, we found that the positively charged antibiotic tobramycin is sequestered to the biofilm periphery, while the neutral antibiotic ciprofloxacin readily penetrated. We provide evidence that tobramycin in the biofilm periphery both stimulated a localized stress response and killed bacteria in these regions but not in the underlying biofilm. Although it is unclear which matrix component binds tobramycin, its penetration was increased by the addition of cations in a dose‐dependent manner, which led to increased biofilm death. These data suggest that ionic interactions of tobramycin with the biofilm matrix limit its penetration. We propose that tobramycin sequestration at the biofilm periphery is an important mechanism in protecting metabolically active cells that lie just below the zone of sequestration.

Are there any relict rock glaciers in the British mountains? - David Jarman; Peter Wilson; Stephan Harrison (Journal of Quaternary Science, 2013)
The existence of a small population of ‘relict rock glaciers’ scattered across the main British mountain areas has previously been inferred from published cases of individual sites or local clusters. Discrete debris accumulations (DDAs) of widely differing character have been identified as ice‐debris landforms (whether ‘rock glaciers’ or ‘protalus lobes’) partly from morphological, sedimentological and topo‐locational evidence, but principally by analogy with both active and relict examples in present‐day arctic/alpine environments, with consequent palaeoclimate inferences. However, re‐interpretation of several supposed rock glaciers as rock slope failures has cast doubt on both the palaeoclimatic reconstructions and the origin of the remaining features. Issues of polygenesis and mimicry/equifinality have contributed to some previous misidentifications. We re‐evaluate the 28 candidate cases based on new field and image‐analysis evidence and place them on a continuum from no ice presence through passive ice presence and glacial shaping to emplacement onto glacier ice with consequent melt‐out topography. A null hypothesis approach (that there are no relict rock glaciers in the British mountains) is pursued, and the evidence indicates that none of the 28 cases clearly warrants classification as a relict rock glacier; their characteristics can be explained without recourse to any significant forward debris movement controlled or facilitated by incorporated or underlying ice as it deforms and melts out. However, only one‐third of the candidate DDAs are attributed in whole or part to rock slope failure ( sensu stricto ), with other debris sources including incremental rockfall, bedrock knolls with coarse debris veneer, protalus rampart and moraine. A few cases deserve more detailed investigation of their structure, morphology and sediments within a broader local glaciological/topographical context, with multitemporal/polygenetic evolution in mind. But it is for future researchers to demonstrate that deforming ice played an incontestable part in shaping these often enigmatic DDAs, given that other causes are simpler and commoner. Copyright © 2013 John Wiley & Sons, Ltd.

Genomic Resources for Evolutionary Studies in the Large, Diverse, Tropical Genus, Begonia - Adrian Christopher Brennan; Stephen Bridgett; Mobina Shaukat Ali; Nicola Harrison; Andrew Matthews; Jaume Pellicer; Alex David Twyford; Catherine Anne Kidner (Tropical Plant Biology, 2012)

A Critical Re-Examination of the Intraluminal Filament MCAO Model: Impact of External Carotid Artery Transection - Rebecca C. Trueman; David J. Harrison; Dominic M. Dwyer; Stephen B. Dunnett; Mathias Hoehn; Tracy D. Farr (Translational Stroke Research, 2011)

Two possible mechanisms of epithelial to mesenchymal transition in invasive ductal breast cancer - Sylvie Dubois-Marshall; Jeremy S. Thomas; Dana Faratian; David J. Harrison; Elad Katz (Clinical & Experimental Metastasis, 2011)

Pacific Rim Forestry / Silviculture and Forest Ecology - Vishal Singh Negi; Archana Pal; Ratnesh Singh; Dulal Borthakur; Archana Pala; Vishal Singh Negi; Dulal Borthakur; Isabel Rushanaedy; Tyler Jones; Nicklos Dudley; Dulal Borthakur; Jannai Yafuso; et al. (Journal of Forestry, 2011)
Leucaena leucocephala (leucaena) is an important agroforestry tree of tropics and subtropics due to its protein rich foliages, ability to grow on poor soils, and high level of tolerance to various stresses including drought and diseases. We hypothesized that leucaena have a unique set of genes which confer tolerance to various abiotic and biotic stresses and these genes are either absent or not expressed in other legumes that are susceptible to these stress conditions. Interspecies suppression subtractive hybridization (iSSH) was performed to identify some unique genes from leucaena using cDNAs from leucaena and Acacia confusa (acacia) as the tester and driver, respectively. We identified 100 leucaena genes showing homology to various plant genes with known functions, of which 23 genes had homology to various stress-related proteins including chitinase, PR-10 protein, wound-stress protein, type-2 metallothionein, thaumatin-like protein, disease resistance response protein, cysteine proteinase, and kunitz trypsin inhibitor. We also identified 50 leucaena genes which either had homology to hypothetical proteins (HyPs) or had no homology at all. Putative functions of 15 HyPs were predicted using conserved domain and PSI-BLAST analyses. Linear motif analyses identified 17 HyPs with MAPK recognition motif, which is involved in signaling pathways, including stress responses. This study identified 23 known and some putative unique stress-related genes from leucaena which may serve as a useful source of stress-tolerance genes for tree and crop improvement in the future.

Niche conservatism as an emerging principle in ecology and conservation biology - John J. Wiens; David D. Ackerly; Andrew P. Allen; Brian L. Anacker; Lauren B. Buckley; Howard V. Cornell; Ellen I. Damschen; T. Jonathan Davies; John‐Arvid Grytnes; Susan P. Harrison; Bradford A. Hawkins; Robert D. Holt; et al. (Ecology Letters, 2010)
The diversity of life is ultimately generated by evolution, and much attention has focused on the rapid evolution of ecological traits. Yet, the tendency for many ecological traits to instead remain similar over time [niche conservatism (NC)] has many consequences for the fundamental patterns and processes studied in ecology and conservation biology. Here, we describe the mounting evidence for the importance of NC to major topics in ecology (e.g. species richness, ecosystem function) and conservation (e.g. climate change, invasive species). We also review other areas where it may be important but has generally been overlooked, in both ecology (e.g. food webs, disease ecology, mutualistic interactions) and conservation (e.g. habitat modification). We summarize methods for testing for NC, and suggest that a commonly used and advocated method (involving a test for phylogenetic signal) is potentially problematic, and describe alternative approaches. We suggest that considering NC: (1) focuses attention on the within‐species processes that cause traits to be conserved over time, (2) emphasizes connections between questions and research areas that are not obviously related (e.g. invasives, global warming, tropical richness), and (3) suggests new areas for research (e.g. why are some clades largely nocturnal? why do related species share diseases?).

Towards an assessment of multiple ecosystem processes and services via functional traits - Francesco de Bello; Sandra Lavorel; Sandra Díaz; Richard Harrington; Johannes H. C. Cornelissen; Richard D. Bardgett; Matty P. Berg; Pablo Cipriotti; Christian K. Feld; Daniel Hering; Pedro Martins da Silva; Simon G. Potts; et al. (Biodiversity and Conservation, 2010)

Orangutan Energetics and the Influence of Fruit Availability in the Nonmasting Peat-swamp Forest of Sabangau, Indonesian Borneo - Mark E. Harrison; Helen C. Morrogh-Bernard; David J. Chivers (International Journal of Primatology, 2010)

Human abuse liability assessment of oxycodone combined with ultra-low-dose naltrexone - David Andrew Tompkins; Ryan K. Lanier; Joseph A. Harrison; Eric C. Strain; George E. Bigelow (Psychopharmacology, 2010)

Novel Integron Gene Cassette Arrays Identified in a Global Collection of Multi-Drug Resistant Non-Typhoidal Salmonella enterica - Mary Krauland; Lee Harrison; David Paterson; Jane Marsh (Current Microbiology, 2010)

An Overview of Global Observing Systems Relevant to GODAE - Candyce Clark; D.E. Harrison; Mike Johnson; Graeme Ball; Howard Freeland; Gustavo Goni; Maria Hood; Michael McPhaden; David Meldrum; Mark Merrifield; Dean Roemmich; Chris Sabine; et al. (Oceanography, 2009)

The influence of riparian buffer strips on carabid beetle (Coleoptera, Carabidae) assemblage structure and diversity in intensively managed grassland fields - Lorna J. Cole; Ruth Morton; William Harrison; David I. McCracken; Duncan Robertson (Biodiversity and Conservation, 2008)

Effects on kidney disease, fertility and development in mice inheriting a protein-truncating Denys-Drash syndrome allele (Wt1 tmT396) - Charles E. Patek; David G. Brownstein; Stewart Fleming; Caroline Wroe; Lorraine Rose; Anna Webb; Rachel L. Berry; Paul S. Devenney; Marion Walker; Oliver D. K. Maddocks; Nicola J. Lawrence; David J. Harrison; et al. (Transgenic Research, 2008)

Potential effects of climate change on DOC release from three different soil types on the Northern Pennines UK: examination using field manipulation experiments - ANTHONY F. HARRISON; KENNETH TAYLOR; ANDY SCOTT; JAN POSKITT; DAVID BENHAM; JOHN GRACE; JACKY CHAPLOW; PHILIP ROWLAND (Global Change Biology, 2008)
Three field manipulation experiments were carried out during 1993–1995 on the Northern Pennines to investigate the influences of temperature, solar radiation and rainfall on the release of dissolved organic carbon (DOC) from vegetated soil cores using zero‐tension lysimeters. The cores were manipulated by being translocated to four sites down a climatic gradient, by artificial soil heating or being exposed to double normal rainfall. In each experiment three soil types, a brown earth, a micropodzol and a peaty gley, with differing organic matter content and distribution within the profile, were studied. DOC data, expressed as mg C m −2 day −1 , were analysed following log 10 transformation, by a repeated measures analysis of variance procedure, using climatic variables measured concurrently with sampling, and 1 and 2 months before sampling. DOC release was dominated by rainfall but was also associated with solar radiation and temperature. With each of the three climatic variables, rainfall, solar radiation and temperature, both positive and negative effects on DOC release have been found significant, indicating that the concurrent and delayed effects of the same variable may be different. DOC release was positively related with all three soils to concurrent rainfall, indicating rainfall's primary leaching action. DOC release was also negatively related to rainfall of the previous month indicating that its action depletes the leachable pool of DOC in the soil. DOC release was positively associated with solar radiation 2 months earlier, indicating that DOC's main source is that of primary production; DOC peaks closely followed peaks of annual primary production. DOC release was linked with temperature, the strongest association being with temperature 2 months earlier, indicating that temperature effects both primary production and DOC regeneration via organic matter decomposition. A conceptual model, relating our findings to those processes known to govern DOC release from soils, has been presented.

Models of anger: contributions from psychophysiology, neuropsychology and the cognitive behavioral perspective - David E. Cox; David W. Harrison (Brain Structure and Function, 2008)

Microarray analysis of gene expression of mouse hepatocytes of different ploidy - Pin Lu; Sandrine Prost; Helen Caldwell; Jonathan D. Tugwood; Graham R. Betton; David J. Harrison (Mammalian Genome, 2007)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Dynamic causal models of neural system dynamics: current state and future extensions - Klaas E Stephan; Lee M Harrison; Stefan J Kiebel; Olivier David; Will D Penny; Karl J Friston (Journal of Biosciences, 2007)

Emotion and Pain: A Functional Cerebral Systems Integration - Gina A. Mollet; David W. Harrison (Neuropsychology Review, 2006)

Oxidant stress—a major cause of reduced endothelial nitric oxide availability in cardiovascular disease - Ulf Landmesser; David G. Harrison; Helmut Drexler (European Journal of Clinical Pharmacology, 2006)

Ecological Footprint Analysis Applied to Mobile Phones - Sibylle D. Frey; David J. Harrison; Eric H. Billett (Journal of Industrial Ecology, 2006)
Ecological footprints (EF) have been used for more than 15 yr as an aggregate measure of sustainability of geographical regions, but also for certain products and activities. EF analysis measures the bioproductive areas required to produce resources such as crops and timber, the directly occupied areas for infrastructure, and areas for absorbing waste flows (mostly limited to carbon dioxide) in a given year for a defined population. The need to extend ecological footprint analysis to electronic products arose because so far, mobile phones have mainly been evaluated using life‐cycle assessments with a focus on toxicity, end‐of‐life management, and energy use, thus ignoring the wider sustainability implications. This article presents the footprint results from three mobile phone case studies. To establish the land areas consumed by the mined materials used in electronic products, a database was developed based on literature data and on approximations from the density and overburden of materials. The relationship between abundance and overburden values was used in a regression analysis to estimate energy requirements in materials extraction where other data were not available. Using a life‐cycle assessment approach, environmental burdens for producing and using a mobile phone were calculated and transformed into the instantaneous rate of resource consumption. Key results were that different electronic products have different ecological footprints and that the methodology proved sensitive enough to reveal differences in small electronic products and for monitoring technologies that use bioproductive space efficiently.

An AFLP-based survey of genetic diversity among accessions of sea oats (Uniola paniculata, Poaceae) from the southeastern Atlantic and Gulf coast states of the United States - Prasanta K. Subudhi; Neil P. Parami; Stephen A. Harrison; Michael D. Materne; J. Paul Murphy; David Nash (Theoretical and Applied Genetics, 2005)

Localisation of NMU1R and NMU2R in human and rat central nervous system and effects of neuromedin-U following central administration in rats - Jane Gartlon; Philip Szekeres; Mark Pullen; Henry M. Sarau; Nambi Aiyar; Usman Shabon; David Michalovich; Klaudia Steplewski; Cathy Ellis; Nabil Elshourbagy; Mark Duxon; Tracey E. Ashmeade; et al. (Psychopharmacology, 2004)

The Neuropsychology of Depression: A Literature Review and Preliminary Model - Brian V. Shenal; David W. Harrison; Heath A. Demaree (Neuropsychology Review, 2003)

exma: an X-linked insertional mutation that disrupts forebrain and eye development - David Cunningham; Qiang Xiao; Aurobindo Chatterjee; Kathleen Sulik; Diana Juriloff; Frederick Elder; Wilbur Harrison; Gabriele Schuster; Paul A. Overbeek; Gail E. Herman (Mammalian Genome, 2002)

Antibiotic resistance in bacteria from magpies ( Pica pica ) and rabbits ( Oryctolagus cuniculus ) from west Wales - David M. Livermore; Marina Warner; Lucinda M. C. Hall; Virve I. Enne; Stephen J. Projan; Paul M. Dunman; Sarah L. Wooster; Graham Harrison (Environmental Microbiology, 2001)
Summary The prevalence of antibiotic‐resistant bacteria in wild animal and bird populations is largely unknown, with little consistency among the few published reports. We therefore examined intestinal bacteria from magpies ( Pica pica ) and rabbits ( Oryctolagus cuniculus ) collected in rural west Wales. Escherichia coli isolates resistant to multiple antibiotics were grown from eight of 20 magpies trapped in spring, 1999 and one of 17 in spring, 2000; the most prevalent resistance trait among these isolates was to tetracycline, but resistances to ampicillin, chloramphenicol, kanamycin, sulphonamide, tetracycline and trimethoprim were also found. Tetracycline‐resistant Enterococcus spp. were found in one of 20 magpies in 1999 and three of 17 in 2000. Only one resistant E. coli isolate was detected among gut bacteria from 13 rabbits, and this strain was resistant only to tetracycline. Differences in the prevalence of resistance between bacteria from rabbits and magpies may reflect differences in diet: rabbits graze field edges, whereas magpies are omnivorous and opportunistic. The resistance genes found in E. coli isolates from magpies mostly corresponded to those common among human isolates, but those conferring tetracycline resistance were unique.

Central effects of urotensin-II following ICV administration in rats - Jane Gartlon; Frederick Parker; David Harrison; Stephen Douglas; Tracey Ashmeade; Graham Riley; Zoe Hughes; Stephen Taylor; Richard Munton; Jim Hagan; Jackie Hunter; Declan Jones (Psychopharmacology, 2001)

Nociceptin/orphanin FQ (N/OFQ) induces a quasi-morphine abstinence syndrome in the rat - David H. Malin; J. Ronald Lake; William D. Moon; Debora Moy; Ana L. Montellano; Edward Moy; Tracy D. Campbell; Maurice V. Bell; Dana Bryant; Laura M. Harrison; David K. Grandy (Psychopharmacology, 2000)

Detection and Quantification of Spongospora subterranea f. sp. subterranea in Soils and on Tubers Using Specific PCR Primers - Kenneth S. Bell; Jane Roberts; Susan Verrall; Daniel W. Cullen; Naomi A. Williams; Julian G. Harrison; Ian K. Toth; David E.L. Cooke; James M. Duncan; Jamie R. Claxton (European Journal of Plant Pathology, 1999)

Effects of climate change on nitrogen dynamics in upland soils. 2. A soil warming study - Philip Ineson; David G. Benham; Janet Poskitt; Anthony F. Harrison; Kenneth Taylor; Clive Woods (Global Change Biology, 1998)
A new warming technique has been developed in a field experimental study of the potential effects of climatic change on N leaching from hill land plant/soil systems. Thermocouple compensating cable has been utilized to provide a small cross‐section, flexible, low voltage heating cable, mounted on a framework of stainless steel mesh, to provide uniform heating at the vegetation/soil interface of zero‐tension lysimeters and surrounding turf. We describe a specially designed heat controller capable of maintaining a temperature differential of 3 °C above ambient at a soil depth of 0.8 cm. The equipment raises temperatures down the soil profile and within the grass sward, whilst tracking normal diurnal temperature variation. Results presented here illustrate the efficacy of the warming technique, together with the consequences for the release of nitrate from lysimeters. The responses of soil solution concentrations of nitrate varied markedly between soil types, but showed a significant decrease in the brown earth during the first 5 months of additional heating. This suggests that increased nutrient release is masked by plant uptake in this soil, but the responses in the other two soils were less marked.

Effects of climate change on nitrogen dynamics in upland soils. 1. A transplant approach - Philip Ineson; Kenneth Taylor; Anthony F. Harrison; Janet Poskitt; David G. Benham; Edward Tipping; Colin Woof (Global Change Biology, 1998)
The impact of climate change on N leaching from hill land plant/soil systems was investigated using a transplant technique involving the movement of intact lysimeter cores of three contrasting soil types down an altitudinal gradient at Great Dun Fell, Cumbria. Air and soil temperatures and precipitation were monitored at four elevations down an altitudinal transect using automatic weather stations for a period of two years. The altitudinal sequence of air temperature followed the anticipated pattern, providing mean annual temperatures at the four locations of 3.4, 5.0, 6.3 and 8.1 °C. Lapse rates of both mean air and soil temperatures over the altitudinal range 171–845 m were 6.6 (1993) and 7.0 °C km –1 (1994). Soil monthly temperature gradients for a particular soil type for each of the two years showed a seasonal range of 6.0 and 7.4 °C km –1 , respectively, and for air temperature of 4.3 and 3.1 °C km –1 . Precipitation gradients showed the expected general increase with altitude, but were less predictable. Inorganic nitrogen leaching was studied in lysimeter leachates with climatic amelioration resulting in dramatic reductions in leachate nitrate concentrations and associated total concentrations of inorganic nitrogen. Decreases in leachate nitrate concentrations were observed for all three soil types studied. Soils receiving supplemented rainfall also showed decreased N concentrations, suggesting that temperature was the main controlling factor responsible for the observed reductions. Increased N uptake by the vegetation, in response to the increases in temperature, is considered to be critical in controlling soil solution chemistry at these sites.

A Neuropsychological Model Relating Self-Awareness to Hostility - Heath A. Demaree; David W. Harrison (Neuropsychology Review, 1997)

Evidence for a role of oxygen-derived free radicals and protein kinase C in nitrate tolerance - T. Münzel; David G. Harrison (Journal of Molecular Medicine, 1997)

Perceptions of Species Abundance, Distribution, and Diversity: Lessons from Four Decades of Sampling on a Government-Managed Reserve - J. Whitfield Gibbons; Vincent J. Burke; Jeffrey E. Lovich; Raymond D. Semlitsch; Tracey D. Tuberville; J. Russell Bodie; Judith L. Greene; Peter H. Niewiarowski; Howard H. Whiteman; David E. Scott; Joseph H. K. Pechmann; Christopher R. Harrison; et al. (Environmental Management, 1997)

The toxicity of copper to the adult and early life stages of the freshwater clam,Corbicula manilensis - Florence L. Harrison; John P. Knezovich; David W. Rice (Archives of Environmental Contamination and Toxicology, 1984)

Determination of the apparent K mfor oxygen of Beneckea natriegens using the respirograph technique - John D. Linton; Alan T. Bull; David E. F. Harrison (Archives of Microbiology, 1977)

Molar growth yields, respiration and cytochrome profiles of Beneckea natriegens when grown under carbon limitation in a chemostat - John D. Linton; David E. F. Harrison; Alan T. Bull (Archives of Microbiology, 1977)

s 60th annual PAA meeting (Part II) - J. Landeo; P. R. Rowe; M. Mayer de Scurrah; M. T. Jackson; P. R. Rowe; J. G. Hawkes; P. Jatala; H. A. Mendoza; F. L. Haynes; G. C. C. Tai; H. Dejong; N. S. Wright; et al. (American Journal of Potato Research, 1976)